Inhibition of histone deacetylases accelerates wound healing in diabetic skin and is associated with vascularization and epidermal tight junction protein expression - Juan Valentin Trujillo-Paez; Adrián Rodríguez-Carlos; Nancy Solís-Torres; Yessica E. Félix-García; Irma González-Curiel; Luis Adrián De Jesús-González; Crisol Rodriguez Mendieta; César Rivas-Santiago; Bruno Rivas-Santiago (Tissue and Cell, 2027)

Collaborative studies on in vitro digestibility of dietary proteins based on the INFOGEST Quant protocol: toward international standardization - Lotti Egger; Ana Blanco-Doval; Cédric Brügger; Raquel Sousa; Lychou Abbühl; Marta Santos Hernández; Beatriz Miralles; Cristina Gómez-Marin; Adam Macierzanka; Patrycja Szumała; Ilona E. Kłosowska-Chomiczewska; Ana Isabel Mulet-Cabero; et al. (Food Research International, 2026)

Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

ALVO: a collective platform for volcanic risk reduction in Latin America - Pablo Forte; Daniel Bertin; Lizzette Rodriguez; Mariana Patricia Jácome Paz; Silvana Hidalgo; Yemerith Alpizar-Segura; Guillermo E. Alvarado; Constanza Perales Moya; José Luis Palma; José G. Viramonte; Hugo Delgado-Granados (Journal of South American Earth Sciences, 2026)

The state of mycology in Honduras - Danny Haelewaters; Libelje Mortier; Tina A. Hofmann; Thomas E. Martin; Johan David Reyes-Chávez; Evelin Y. Reyes-Mendez; Stephanie Yelenia Rodriguez Ordoñez; Elia Martha Sarmiento Sánchez; Jeffery K. Stallman; Bryan Ortiz (Fungal Ecology, 2026)

A scoring system for validity assessment of biomarkers of food intake - Christoph Hassenberg; Carina I. Mack; Claudia Favari; Sylvie Baier; Ramon Estruch; Gabi Kastenmüller; Rosa Lamuela-Raventós; Rikard Landberg; Pedro Mena; Costanza Michelini; Stefania Noerman; Ana Rodriguez-Mateos; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Importance of Single Global Regulatory Standards for the Assessment of Generic and Biosimilar Medicines to Advance Patient Access - Antonela Rodriguez; Vishalakshi Krishnan; James E. Polli; Anna Schwendeman (The AAPS Journal, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

First report of phthalate acid esters (plasticizers) in blubber of southern right whales (Eubalaena australis) from Península Valdés, Argentina - Luciana Gallo; Melina Paola Michlig; Maria Rosa Repetti; Agustina Donini; Adrian E. Rodriguez; Mariano Sironi; Marcela M. Uhart (Polar Biology, 2026)
Phthalate acid esters (PAEs) are widely used plastic additives that have become ubiquitous contaminants in marine environments. Filter-feeding baleen whales may be exposed to these pollutants through water, prey or ingested plastic debris. While macroplastics have been reported in the gut of a southern right whale (SRW, Eubalaena australis ), exposure to PAEs has not been assessed. Here, we quantified three lipophilic PAEs, dimethyl phthalate (DMP), dibutyl phthalate (DBP), and di-2-ethylhexyl phthalate (DEHP), in the blubber of 13 SRWs (three calves, three juveniles and seven adults) stranded in 2021 at Península Valdés, Argentina. More than 90% of samples contained detectable PAE levels, and 46.2% were above quantification limits. DEHP and DBP were the most prevalent compounds (61.5% and 30.8%, respectively), although the biological significance of the detected concentrations remains uncertain. This is the first report of PAEs in SRW blubber and suggests potential mother-calf transfer, highlighting exposure of Southern Hemisphere mysticetes to plastic-derived chemicals.

Seasonal changes in the impact of infauna on sediment physical properties - Chesna E. Cox; Kelly M. Dorgan; Nina Stark; Adrian Rodriguez-Marek; Grace Massey; Carl Friedrichs; Md Rejwanur Rahman (Geo-Marine Letters, 2026)

A low-cost imaging platform for quantitative characterisation of scaffold surface macrotopography with potential application in craniofacial tissue engineering - X. Marimon; E. Saman-Sakkal; R. Rodriguez; A. Portela; M. Cerrolaza; M. A. Mateos; R. Pérez (Medical & Biological Engineering & Computing, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Leveraging outstanding first records to advance invasion science - A. Bortolus; L. A. Meyerson; M. A. Rodriguez-Cabal; E. Schwindt (Biological Invasions, 2026)

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Pinolidoxin production by Ascochyta pinodes during pea infection: Insights from in planta metabolomics - Pierluigi Reveglia; Sara Rodriguez-Mena; José E. Yuste; Lucia Lecce; Diego Rubiales; Eleonora Barilli (Physiological and Molecular Plant Pathology, 2026)

Relationships between gluten proteins and texture in low-hydration dough - Jeffrey Eiseman; Byung-Kee Baik; Osvaldo Campanella; Luis E. Rodriguez-Saona; Emmanuel Hatzakis (Food Research International, 2026)

Optimization of Agrobacterium-mediated transformation of commercial heirloom tomato cultivars to develop novel traits via CRISPR/Cas9 genome editing - Jordan Oxendine; Elsa Ibarra-Reyes; Junchi Ma; Carrie Li; Sarah Baron; Allison E. Hwang; Ruiting Wang; Daniel Rodriguez-Leal (Planta, 2026)
Main conclusion Trait development for commercial heirloom tomatoes can be advanced by optimization of tissue culture and transformation via Agrobacterium and CRISPR/Cas9 mutagenesis. Abstract Genetic improvement using new genome editing approaches relies on the efficient delivery of the CRISPR/Cas system in the vegetable crop tomato. Previous protocols for tomato transformation have primarily focused on a handful of cultivars (M82, Ailsa Craig, Microtom, Sweet-100) with very little commercial relevance, and it is not clear if these protocols can be implemented directly in other commercially relevant varieties. Heirloom tomatoes are sought for their deep and diverse flavor but have not been subjected to systematic crop improvement via conventional breeding or biotechnology approaches such as transgenesis or genome editing. Therefore, we tested the transformation and regeneration capacity of six different heirloom cultivars known for their superior taste and market relevance in the US. Subsequently, we optimized rooting conditions and used the GRF4-GIF1 chimeric developmental regulator to successfully recover transgenic plants. Finally, we evaluated the efficiency of targeted genetic modification using the CRISPR/Cas9 genome editing system in several of these cultivars. We demonstrate that our optimizations led to successful transformation of several heirloom varieties, including the generation of edited plants for target genes modifying plant architecture and flowering time. Our results set the foundation for a biotechnology platform to deliver improved traits to local and regional heirloom varieties using genome editing.

Biocrust belt below the edge of a dying glacier in the Tropical Andes - Alejandro Salazar; Maria E. Gutiérrez-Lagoueyte; Ingibjörg S. Jónsdóttir; Isabel C. Barrio; Heiðrún I. Guðmundsdóttir; Emilio Rodriguez-Caballero; Adriana Sanchez (Alpine Botany, 2026)
On recently deglaciated terrain, soil instability can be a physical barrier limiting seedling establishment. Here we used a space-for-time approach to study the role of biological soil crust (biocrust) as soil surface stabilizer and facilitator of ecological succession along a glacier forefield chronosequence at the retreating Conejeras glacier in the Tropical Andes. We used the point-intercept method to estimate surface cover of plants, biocrust, bare ground and rocks, as well as soil surface roughness; and a field soil aggregate kit to estimate soil stability. As hypothesized, following a bare-ground stage near the edge of the glacier, the successional trajectory involved the development of a biocrust belt, including bryophytes and lichens, followed by an increasing vascular plant cover. The development of biocrust was accompanied by higher soil surface roughness and soil stability, which likely increased seed entrapment and seedling establishment. Our results suggest that the development of cyanobacterial-dominated biocrust at the forefield of the Conejeras glacier may favor the establishment of plants with large seeds, such as graminoids from the Festuca genus. Overall, our findings highlight the key role of biocrusts in the ecological dynamics that follow glacier melt in the Tropical Andes.

In silico and experimental characterization of fipronil–membrane interactions: Implications for pesticide selectivity - Marcos A. Asis-Rodriguez; Mariela E. Sánchez-Borzone; Daniel A. García; Virginia Miguel (Pesticide Biochemistry and Physiology, 2026)

Uncovering how major extracellular proteins drive virulence and functional compensation in the mollusk pathogen Vibrio europaeus - Clara Martínez; Sergio Rodriguez; Alba Trueba; Diego Rey-Varela; Alicia E. Toranzo; Ana L. Dieguez; Javier Dubert (Journal of Invertebrate Pathology, 2026)

Per- and polyfluoroalkyl substances and pesticides in black bears (Ursus americanus) and grizzly bears (Ursus arctos horribilis) from Montana's Cabinet-Yaak ecosystem: A baseline assessment of emerging and legacy contaminants - Brian C. Balmer; Marina D. Rodriguez; Justin E. Teisberg; Michelle L. Hladik; Wayne F. Kasworm; Amber Kornak; Thomas G. Radandt; Landon M. Keele; Erin L. Pulster (Environmental Pollution, 2026)

Climatic Niche Modelling Reveals Limited Phylogenetic Niche Conservatism in New World Crocodylians - Andrés L. Rodriguez‐Cordero; Nancy E. McIntyre; Richard D. Stevens; Joseph D. Manthey; Carlos Portillo‐Quintero; Natasja Van Gestel; Sergio A. Balaguera‐Reina; Brandon A. Gross; Margaret Munn; Llewellyn D. Densmore (Journal of Biogeography, 2026)
Aim Phylogenetic niche conservatism, the tendency of closely related species to retain ancestral ecological traits, has gained considerable interest, yet the lack of integration across independent evaluation methods has hindered our understanding of whether niches are conserved or dynamic. Such an understanding is especially relevant for taxa of conservation concern, such as crocodylians (order Crocodylia). This study assessed niche conservatism among New World crocodylians by combining ensemble species distribution models, phylogenetics, and standard metrics of geographic and environmental niche overlap. Location America. Major Taxa Order Crocodylia. Methods We estimated species' climatic niches in geographic and environmental dimensions to assess overlap patterns and quantified associations between niche overlap and phylogenetic patristic distance using the Mantel test and phylogenetic independent contrast (PIC). Results Overlap analyses in geographic and environmental spaces revealed climatic niche differentiation across the clade, suggesting divergent environmental preferences among species. The relationship between phylogenetic patristic distance and climatic niche overlap assessed via Mantel tests revealed a significant negative correlation with geographic niche overlap ( ρ = −0.361, p = 0.005), but no evidence for associations with environmental niche overlap (Schoener's D: ρ = −0.079, p = 0.184; Hellinger's I: ρ = −0.063, p = 0.250), suggesting that more distantly related species overlap less geographically. In contrast, the relationship assessed using PIC revealed no evidence for associations between phylogenetic distance and either geographic ( ρ = −0.200, p = 0.579) or environmental niche overlap (D: ρ = −0.294, p = 0.41; I: ρ = −0.319, p = 0.369). Conclusions We found no strong or consistent evidence for phylogenetic conservatism in climatic niches across both geographic (inverse relationship) and environmental (no relationship) dimensions in New World crocodylians. This study enhances our understanding of niche dynamics and highlights the value of integrating niche modelling with phylogenetic analyses to detect biogeographic and evolutionary patterns.

Comparative evaluation of sperm quality assessment methods in purebred spanish horses - N. Latorre; C. Gómez-Cuétara; E. Cañizares; F. Crespo; V. Pérez-Aguilera; M. Iniesta Cuerda; J.A. Laborda-Gomariz; A.J. Soler; E.R.S. Roldan; A. Sanchez-Rodriguez (Journal of Equine Veterinary Science, 2026)

Germination and toasting shape composition and sensory quality of black creole maize flours for atole - Margarita I. Hernández-Urbiola; Mariana Ponce-Mendoza; Ezequiel Hernández-Becerra; Marcela Gaytán-Martínez; Edgar A. Esquivel-Fajardo; Fernanda Martinez-Hernandez; Oscar Y. Barrón-García; Mario E. Rodriguez-Garcia (Food and Humanity, 2026)

Morphology and particle size distribution in the indoor dust: A hidden threat to human health? - D. Meza-Figueroa; E. Vega; J. Entwistle; A. Angulo-Molina; A. Valencia-Meza; B. Schiavo; V. Rodriguez; B. González-Grijalva; F. Berrellez-Reyes; C. Ortega-Rosas; A. Wellens; A. Namdeo (Environmental Geochemistry and Health, 2026)

Ground level enhancement GLE #77 on 11 November 2025: a data summary - A.L. Mishev; B. Heber; K.-L. Klein; R. Vainio; H. Mavromichalaki; O. Raukunen; N. Larsen; N. Petrov; N. Nikonov; S. Masson; M. Pesce-Rollins; B.T. Kress; et al. (Advances in Space Research, 2026)

Exposure to low-dose ionizing radiation and dementia mortality in Canadian nuclear power plant workers - Brianna Frangione; Laura A. Rodriguez Villamizar; Ian Colman; Franco Momoli; Estelle Davesne; Lydia Zablotska; Cheryl E. Peters; Paul Demers; Minh Do; Tim Prendergast; Philippe Prince; Paul J. Villeneuve (Environmental Research, 2026)

Petiole Nitrate Analysis: A Diagnostic Method for Optimizing Nitrogen Management in Potato - C. M. Giletto; W. Carciochi; S. E. Silva; M. N. Cassino; S. Rodriguez; J. C. Laborde Amador; E. C. Zamuner; N. I. Reussi Calvo (Potato Research, 2026)

Decoupled Climatic Drivers of Tree and Ground‐Layer Carbon Uptake in Mountain Ecosystems Around the World - Max Mallen‐Cooper; Maja K. Sundqvist; David A. Wardle; Radim Šarlej; Rose E. Brinkhoff; Aimée T. Classen; Eliška Kuťáková; Daniel B. Metcalfe; M. Noelia Barrios‐Garcia; Julie R. Deslippe; Kobayashi Makoto; Jane Mallen‐Cooper; et al. (Global Change Biology, 2026)
One of the key ecological processes affected by climate change is plant carbon uptake. However, there is substantial uncertainty about how plant carbon uptake will respond to warming in mountain ecosystems, which are known for sharp temperature gradients and abrupt shifts in vegetation structure. Specifically, we lack an understanding of whether these response trajectories over time will be linear or non‐linear, and how they might vary among mountain ecosystems globally. Here, we measured ecosystem Gross Primary Productivity (GPP) along forest‐tundra elevational gradients in the mountain regions of five countries (Argentina, Australia, France, Sweden, USA) to infer future trajectories of carbon uptake, and whether any non‐linear changes might occur. We also examined the role of microclimate in driving GPP responses. We found that whole‐ecosystem GPP increased with increasing macroclimatic temperature (decreasing elevation), but this response was dominated by a sharp non‐linear increase at the transition from tundra to forest (i.e., the treeline). In contrast, ground‐layer GPP was largely independent of macroclimate, but often responded strongly, and linearly, to microclimate (growing degree days > 5°C, mean growing season temperature). This pattern reflected a frequent decoupling of microclimate from the expected temperature‐elevation relationship, likely driven by such processes as cold‐air drainage, limited near‐surface air mixing, and shading by trees. The contrasting responses of GPP among global temperature gradients indicates strong context dependence at both local and continental scales, although in a few cases, biomass and leaf nitrogen were important moderators. These findings suggest that future shifts in carbon uptake in mountains will be mainly controlled by tree range expansion. Our results highlight the need to consider species responses on different spatial scales, and to increase representation of undersampled regions to capture the full breadth of ecological responses to climate change.

Expanding the arsenal: non-conventional insecticides for managing pyrethroid-resistant Aedes aegypti - Daniela Cerda-Apresa; Selene M. Gutierrez-Rodriguez; Jesus A. Davila-Barboza; Iram P. Rodriguez-Sanchez; Victoria Pando-Robles; Beatriz Lopez-Monroy; Humberto Quiroz-Martinez; Guadalupe Rojas-Verde; Adriana E. Flores (International Journal of Tropical Insect Science, 2026)

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Human-machine Interface using functional electrostimulation and inertial sensors for lower limb rehabilitation in spinal cord injury individuals: a proof of concept - Luiz Henrique Bertucci Borges; Cristian Felipe Blanco-Díaz; Bruno Henrique e Silva Bezerra; Caroline Cunha do Espírito Santo; Teodiano Bastos-Filho; Denis Delisle-Rodriguez; André Felipe Oliveira de Azevedo Dantas (Medical & Biological Engineering & Computing, 2026)
A spinal cord injury (SCI) is a neurological disorder that impairs motor and physiological functions and leads to a reduced quality of life and autonomy for the person affected. In this scenario, human-machine interfaces (HMIs) have emerged as an effective tool to leverage residual motor capabilities and benefit injured persons. This work aims to develop a closed-loop HMI system for lower-limb rehabilitation composed of an in-house multi-channel Functional Electrical Stimulation (FES), which is activated by considering gait and pedaling cycles measured by an Inertial Measurement Unit. Two experiments were conducted with individuals suffering partial SCI who performed cycling and walking activities by using our proposed HMI, while inertial and electroencephalography signals were collected for further analysis and validation. Relative power changes were observed in mu (8–13 Hz) and high beta (20–30 Hz) bands over the foot area (Cz location), comparing both FES and non-FES conditions during gait and pedaling. This comparison also showed that the volunteers performed physical activities with greater speed and cadence by using the proposed HMI system, which correctly identified the movement phases. Graphical abstract A spinal cord injury (SCI) is a neurological disorder that impairs motor and physiological functions, leading to reduced quality of life and autonomy for affected individuals. In this context, human–machine interfaces (HMIs) have emerged as effective tools to enhance residual motor capabilities and support rehabilitation. This study aims to develop a closed-loop HMI system for lower-limb rehabilitation composed of an in-house multi-channel Functional Electrical Stimulation (FES) device, activated based on gait and pedaling cycles measured by an Inertial Measurement Unit (IMU). Two experiments were conducted with individuals with partial SCI who performed cycling and walking tasks using the proposed HMI system, while inertial and electroencephalography (EEG) signals were recorded for further analysis and validation. Relative power changes were observed in the mu (8–13 Hz) and high beta (20–30 Hz) bands over the foot area (Cz location) when comparing FES and non-FES conditions during gait and pedaling. This comparison also revealed that participants performed physical activities with greater speed and cadence when using the proposed HMI system, which successfully identified movement phases in real time.

Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

Governance Arrangements That Fit Social‐Ecological Context Are Associated With Fishery Sustainability - Mateja Nenadović; Alfredo Giron; Timothy Frawley; Adrian Munguia‐Vega; Kara E. Pellowe; Erica Ferrer; David Gill; Blanca González‐Mon; Andrew F. Johnson; Emilie Lindkvist; Fiorenza Micheli; Amy H. Weaver; et al. (Fish and Fisheries, 2026)
In many parts of the world, natural resources are primarily managed by governance arrangements at the local level. Those arrangements range from collective, such as cooperatives and associations, to individualistic, such as patrons and owner‐operators. A key question is how such arrangements influence resource use and associated social and ecological outcomes. We hypothesize that sustainable resource use is not associated with a specific governance arrangement, but instead that every type of arrangement has a certain set of social and ecological conditions under which sustainable resource use is feasible. This hypothesis was empirically investigated using fisheries landings data from Mexico. We found that sustainable resource use can be achieved through multiple governance arrangements provided that they are matched to appropriate social‐ecological contexts. Our findings help identify which governance arrangements are best suited to particular contexts and provide the initial building blocks for developing a theory of governance contextual fit in social‐ecological fishing systems.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Nationwide integrative analysis of pyrethroid resistance in Aedes aegypti from Mexico - Kevin A. Ontiveros-Zapata; Alan E. Juache-Villagrana; Selene M. Gutierrez-Rodriguez; Jesus A. Davila-Barboza; Iram P. Rodriguez-Sanchez; Beatriz Lopez-Monroy; Magaly Romero-Villarreal; Emma Gomez-Ruiz; Adriana E. Flores (Pesticide Biochemistry and Physiology, 2026)

Correction to: The Neuronal Ischemic Tolerance Is Conditioned by the Tp53 Arg72Pro Polymorphism - Maria E. Ramos-Araque; Cristina Rodriguez; Rebeca Vecino; Elisa Cortijo Garcia; Mercedes de Lera Alfonso; Mercedes Sanchez Barba; Laura Colàs-Campàs; Francisco Purroy; Juan F. Arenillas; Angeles Almeida; Maria Delgado-Esteban (Translational Stroke Research, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Correction: Gut microbial communities of Rocky Mountain Sculpin (Cottus bondi) and suckerfish (Catostomus spp.) in the East Gallatin River - Maria L Rodriguez; Andrew J Maritan; Christine E Verhille; Frank J Stewart; Deborah E Keil; Augustus Armijo; Zoe A Pratte (Frontiers in Marine Science, 2026)

Correction to: Multiple exposure pathways to pesticide residues in tropical agroecosystems: A human health risk assessment in Costa Rica - José R. Montiel‑Mora; Greivin Perez‑Rojas; Laura Brenes‑Alfaro; Carlos E. Rodriguez‑Rodriguez (Environmental Monitoring and Assessment, 2026)

First Detection of the L1014F kdr Mutation in Triatoma dimidiata, a Vector of Chagas Disease in Mexico - Jesus A. Davila-Barboza; Selene M. Gutierrez-Rodriguez; Iram P. Rodriguez-Sanchez; Adriana E. Flores (Neotropical Entomology, 2026)

Impacts of Diverse Stakeholder Participation on Fisheries Management - Sangeeta Mangubhai; S. L. Smith; Z. Davis; N. Koedyker; J. Augustyn; D. Durholtz; S. Fulton; Harlisa; M. T. Hidayat; L. Hiriart-Bertrand; M. Khazali; E. Litsinger; et al. (Coastal Management, 2026)

Identifying and quantifying greenhouse gas emissions with the AVIRIS-3 airborne imaging spectrometer - Red Willow Coleman; Andrew K. Thorpe; Philip G. Brodrick; Adam Chlus; Jay E. Fahlen; Brian Bue; John Chapman; Regina F. Eckert; Daniel J. Jensen; Michael L. Eastwood; David R. Thompson; Clayton D. Elder; et al. (Remote Sensing of Environment, 2026)

The rhythms of environmental conditions, particles dynamics, and barnacle activity captured by underwater imaging in sub-Antarctic kelp forests of the Beagle Channel - E. Trudnowska; P. Balazy; M. Bagur; P. Kuklinski; J. Kaminsky; K. Balazy; M. Rodriguez; Z. Derwich; G. Lovrich (Progress in Oceanography, 2026)

The effect of clay minerals on Li in martian groundwater simulant - Rachel Y. Sheppard; Jessica M. Weber; Laura E. Rodriguez; Cathy Trejo; Elisabeth M. Hausrath; Laura M. Barge (Icarus, 2026)

Impact of high-amylose starch addition on the resistant starch content and the physicochemical properties of maize (Zea mays L.) cookies - Ludy M. Martinez-Rubio; Ivan Luzardo-Ocampo; Oscar Y. Barrón-García; Mario E. Rodriguez-García; Guadalupe Loarca-Piña; Marcela Gaytán-Martínez (Food Chemistry, 2026)

Use of shotgun immunoproteomics for the development of protein vaccines against Edwardsiella piscicida - Kim L. Jacobsen; Matt J. Griffin; Brett S. Phinney; Michelle Salemi; Zeinab Yazdi; Sujita Balami; Caitlin E. Older; Cynthia C. Ware; Fernando Y. Yamamoto; Noor-ul Huda; Tania Rodriguez-Ramos; Brian Dixon; et al. (Fish & Shellfish Immunology, 2026)

Two species and two karyotypes? Cytogenetic differentiation between Passiflora foetida L. and P. vesicaria L. (Passifloraceae) - Bruna Zirpoli; Arthur Monteiro; Pablo E. Rodriguez; Bruno Leal Viana; Jefferson Rodrigues Maciel; Andrea Pedrosa-Harand; Mariela A. Sader (Systematics and Biodiversity, 2025)

Integrative systematics of the Brazilian tree “sucupira”: morphological, cytogenetic and genomic boundaries of Pterodon emarginatus Vogel and P. pubescens (Benth.) Benth. (Leguminosae, Papilionoideae) - Victória B. Albernaz; Yennifer Mata-Sucre; Mariela A. Sader; Pablo E. Rodriguez; Cíntia P. Targueta; Adriana M. Antunes; Rafael B. Pinto; André Marques; Dulce Maria Sucena D. A. Rocha; Gustavo Souza; Thannya N. Soares (Systematics and Biodiversity, 2025)

Gut microbial communities of Rocky Mountain Sculpin (Cottus bondi) and suckerfish (Catostomus spp.) in the East Gallatin River - Maria L Rodriguez; Andrew J Maritan; Christine E Verhille; Frank J Stewart; Deborah E Keil; Augustus Armijo; Zoe A Pratte (Frontiers in Marine Science, 2025)
The gastrointestinal (GI) microbiome plays a critical role in animal health and fitness, yet it remains understudied in many species—particularly those inhabiting freshwater environments affected by anthropogenic activity. This study investigates the gut microbiomes of two benthic fish species, Rocky Mountain Sculpin ( Cottus bondi ) and suckerfish ( Catostomus spp.), collected upstream and downstream of a wastewater treatment plant (WWTP) effluent outflow into the East Gallatin River in southwestern Montana. Prokaryotic and eukaryotic microbiome diversity in the fish GI tract was assessed using 16S and 18S rRNA gene sequencing, respectively, from samples collected in the summer and fall of 2022 and 2023. While alpha diversity only had insignificant and small shifts across samples, beta diversity (taxonomic composition) differed significantly across sites and collection dates. Notably, the composition of eukaryotic sequences shifted markedly from upstream to downstream locations, suggesting that WWTP effluents may influence both prokaryotic and eukaryotic microbial communities. By establishing baseline GI microbiome characteristics for these species, this study provides important insights into the potential ecological effects of wastewater discharge on freshwater systems and supports conservation efforts aimed at mitigating pollutant impacts.

The Guajira contourite depositional system along the northern Colombian Caribbean convergent margin - J. Naranjo-Vesga; O. Mantilla; D. Rincón-Martínez; E. Rodriguez-Rubio; A. Ortiz-Karpf; C. Winter; Y. Rojas-Agramonte (Marine and Petroleum Geology, 2025)

Physicochemical characterization of isolated nanocrystals in starch and isolated rice starch: A new perspective - Porfirio E. Martinez-Munoz; Elsa Gutierrez-Cortez; Margarita I. Hernandez-Urbiola; Adriana Lopez-Leon; Oscar Y. Barron-Garcia; Mario E. Rodriguez-Garcia (Food Chemistry, 2025)

A Simple Model to Estimate the Economic Optimum Nitrogen Rate in Potato Using Vegetation Indices - Claudia M. Giletto; W. D. Carciochi; F. M. Inchauspe; S. E. Silva; M. N. Cassino; V. Ortega; S. Rodriguez; J. C. Laborde Amador; N. Reussi Calvo (Potato Research, 2025)

Integrative metabolomic and transcriptomic analysis reveals CYP450-driven biosynthesis of pentacyclic triterpene acids in Cecropia angustifolia - Juan E. Vivas-Moncayo; Paula C. Muñoz-Bonilla; Laura M. Rodriguez-Santa; Adrián C. Rodriguez-Ararat; Guillermo Montoya (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)
Pentacyclic triterpene acids (PTAs) are specialized plant metabolites known for their anti-inflammatory and antidiabetic preclinical reports. Cecropia angustifolia , a prominent species in the Andean montane forests, produces a variety of PTAs in its roots, but little is known about enzymes responsible for their oxidative structural decorations. In this study, we explored the biosynthetic route of PTAs oxidation by cytochrome P450 (P450s) enzymes, comparing wild-collected and in-vitro cultivated root tissues. Chemical profiling was carried out using targeted metabolomics to assess PTAs in both types of extracts. Oxidation patterns differed between the samples, suggesting distinct enzyme activity depending on growth conditions. To support these findings, we assembled a de novo transcriptome based on publicly available Cecropia RNA-seq data and predicted over 26,000 open reading frames. Four P450 families (CYP716A, CYP716C, CYP72A, and CYP71D) are potential contributors to triterpene oxidation, which were identified by homology-based annotation. Gene expression was examined by RT-qPCR, revealing differential transcriptional activity between wild and in-vitro roots. Nevertheless, these differences link the gene expression profile of P450s involved in this pathway to the TPAs metabolic expression. Notably, despite changes in expression, the capacity to generate oxidized PTAs was retained under both conditions. Our results indicate that the oxidative metabolism of triterpenes in C. angustifolia is largely conserved and responsive to environmental cues. This study enhances the current understanding of PTA biosynthesis and supports the use of in-vitro systems as a practical strategy to obtain valuable metabolites while minimizing ecological impact.

Correction to: Hydrogeochemical Evaluation of an Urban Aquifer Under Stress: Rare Earth Elements Fractionation and Human Health Implications - K. M. Ochoa-Guerrero; P. F. Rodriguez-Espinosa; E. Martinez-Tavera; V. Balaram; M. P. Jonathan (Environmental Management, 2025)

Hydrogeochemical Evaluation of an Urban Aquifer Under Stress: Rare Earth Elements Fractionation and Human Health Implications - K. M. Ochoa-Guerrero; P. F. Rodriguez-Espinosa; E. Martinez-Tavera; V. Balaram; M. P. Jonathan (Environmental Management, 2025)

The role of emersion time in modulating biomarker responses to pollution in intertidal mollusks - María V. Laitano; Clara Liebana; Ivana S. Friedman; Yamila E. Rodriguez (Marine Environmental Research, 2025)

Assessment of microplastic retention efficiency using pilot-scale filtration systems applied to drinking water - K. Herrera; A. Egea-Corbacho; D. Coello; J. Quiroga; E. Marin; V. Monsalvo; E. Lucero; R. Rodriguez (Journal of Hazardous Materials, 2025)

Evaluation of potassium bromate as a positive control in the in vivo Fpg-modified comet assay for the detection of oxidised bases - E. Saenz-Martinez; M. Collia; A. Rodriguez-Garraus; A.G. Gil; A. Lopez de Cerain; A. Azqueta (Food and Chemical Toxicology, 2025)

“Effects of mercury exposure in three Amazonian agricultural plant species and the impact on bacterial population in soil” - Maria J. Rodriguez-Pascual; Claudia Vega; Natasha Andrade; Luis E. Fernández; Shih-Huai Cheng; Birthe Kjellerup; Alba Torrents (Environmental Research, 2025)

Ecological Risk–Benefit Analysis for Assisted Colonization - Rafael D'Andrea; György Barabás; Sarah E. Dalrymple; Wendy Foden; Piero Genovesi; Meghna Krishnadas; Mathew A. Leibold; Mark A. McPeek; Axel Moehrenschlager; Jon Paul Rodriguez; H. Reşit Akçakaya (Global Change Biology, 2025)
Assisted colonization (AC), translocating a species outside its indigenous range to avoid its extinction, is one of the few conservation options for some species. It is also controversial because of the history of ecological impacts of invasive species, including the extinction of native species as a result of novel ecological interactions resulting from the introduction. Although several national and international organizations have issued guidelines related to AC, none allow case‐specific decision‐making based on risks and benefits to biodiversity. We propose a two‐pronged approach to fill this gap. The first step aims to separate clear‐cut cases of AC from those that require an in‐depth risk analysis. We propose a set of seven qualitative criteria to identify AC projects that are clearly low‐risk and high‐benefit, and therefore should not be controversial, and those that are clearly high‐risk or low‐benefit and therefore should not be attempted. This identifies only the most obvious cases, leaving out many cases to be determined through a quantitative analysis to estimate the probabilities of extirpation of the resident species because of AC, which is the second step of our approach. We propose a roadmap for developing such a system based on community ecology theory, and a framework for considering the estimated probabilities in a global context. Our framework recommends an AC project only if it would result in a larger number of globally extant species than a scenario of no action. We propose large‐scale testing of the clear‐cut approach, further development of the quantitative approach, and wide consultation for adopting international guidelines for risk assessment of AC projects.

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Evaluation of a semi-analytical bimodal Gaussian model for the estimation of the lateral velocity distribution behind a tidal stream turbine - Wei Zang; Yuquan Zhang; Yuan Zheng; Chengyi Li; E. Fernandez-Rodriguez; Lianchen Xu (Ocean Engineering, 2025)

Food Security and Awareness of the Campus Health Environment: Investigating College Students' Perspectives - A. Rodriguez; A. Lewis; E. McKinley (Journal of the Academy of Nutrition and Dietetics, 2025)

Hydrogeochemical behavior and seasonal fractionation of rare earth elements in a volcanic river system influenced by natural and human factors, central Mexico - K.M. Ochoa-Guerrero; P.F. Rodriguez-Espinosa; E. Martinez-Tavera; Chidambaram Sabarathinam; S.B. Sujitha; H. Hérnandez-Mendoza; Bedour Alsabti (Journal of South American Earth Sciences, 2025)

Cell biology features and gene expression programs modulating cell expansion during root organ growth - Camila Goldy; Virginia Barrera; Mariana Sotelo-Silveira; Ramiro E. Rodriguez (Current Opinion in Plant Biology, 2025)

Nutritional Ecology of Lactation in Franciscana Dolphins ( Pontoporia blainvillei ) From Argentina - Pablo Denuncio; M. Candela Macagno; Antonella D. Padula; M. Agustina Mandiola; Juan P. Loureiro; María Julieta Olocco Diz; M. Fernanda Zapata; Diego Rodriguez; Gabriel E. Machovsky‐Capuska (Marine Mammal Science, 2025)
Milk production strategies, duration, and composition vary among mammals. Odontocete cetaceans exhibit a long lactation strategy characterized by high parental investment and prolonged nutritional dependence. Understanding the nutritional demands of these offspring during lactation is complex, particularly due to their aquatic lifestyle. This study examines the nutritional dynamics of endangered Franciscana dolphins ( Pontoporia blainvillei ) during their first year of life. Our findings indicate that Franciscana milk is energy‐rich, with proteins and lipids as primary energy sources, varying in proportion throughout lactation. Summer milk has a higher protein‐to‐lipid ratio and lower energy density, while winter milk is more energy‐dense, with a greater lipid proportion and increased variability in composition. Calves over 80 cm consume a combination of low protein‐to‐lipid ratio milk with high protein‐to‐lipid ratio prey. Artificial milk formulas used in rehabilitation closely resemble the macronutrient composition of wild milk. This study provides valuable insights into the critical life stage of this vulnerable species and contributes to developing nutritional protocols for rehabilitating live‐stranded individuals.

The Bermuda Triangle of paediatric brain cancers: epigenetics, developmental timing window and cell of origin - Afraah Cassim; Yolanda Colino-Sanguino; Sarah L. Fox; Laura Rodriguez de la Fuente; Hannah E. Hartley; Fatima Valdes-Mora (Cancer and Metastasis Reviews, 2025)
Paediatric brain cancers are aggressive tumours that urgently need deeper understanding of their cellular and molecular vulnerabilities to facilitate the development of effective treatments. These tumours frequently arise from epigenetic alterations in specific immature cell states of the developing prenatal or neonatal brain. In this review, we propose a “three-event” model composed of an epigenetic event, developmental timing window and the cell of origin for tumour initiation in paediatric brain tumours. We focus on three types of paediatric gliomas: diffuse midline gliomas (DMG), diffuse hemispheric gliomas (DHG) and posterior fossa A ependymomas (PFA-EPN), which reflect our proposed three-event model. Additionally, we discuss the methods and models used to study these three events separately or simultaneously. Taken together, this review highlights the spatio-temporal vulnerable cell states during brain development and which molecular drivers hijack these cues to induce cell state stalling and tumour initiation. The next steps to expand our understanding of the order of events and their use in therapy are further discussed.

Phosphorus-responsive fungi associated with roots of Uruguayan native grassland plants: a microcosm study with two herbs and two grasses - Natalia E. Rodriguez Rodriguez; Rebeca Gonnet; Diego Michelini; Tamara Fernández-Calero; Hugo Naya; Andrea Rodríguez-Blanco (Rhizosphere, 2025)

Optimizing forest planning: Balancing timber production and carbon sequestration through a multi-objective disjunctive formulation - Frank Piedra-Jimenez; Diego Broz; Juan M. Novas; Ignacio E. Grossmann; Maria Analia Rodriguez (Forest Policy and Economics, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Reconstructing the Holocene volcanic past of El Hierro, Canary Islands - C. Prieto-Torrell; J.L. Fernandez-Turiel; A. Rodriguez-Gonzalez; M. Aulinas; E. Beamud; M.C. Cabrera; C. Criado; H. Guillou; P. Vidal-Matutano; F.J. Perez-Torrado (Quaternary Geochronology, 2025)

Optical and particulate properties of dust aerosols in El Paso, Texas - German Rodriguez Ortiz; Manisha Mehra; Mackenzie Ramirez; Sujan Shrestha; Sascha Usenko; James Flynn; Rebecca J. Sheesley; Thomas E. Gill (Atmospheric Research, 2025)

Biophysical and biochemical limitations to photosynthesis and yield of peanut (Arachis hypogaea L.) under water-deficit stress - Bishwoyog Bhattarai; Harsimran Kaur-Kapoor; Alexander Rodriguez; Mark D. Burow; Glen L. Ritchie; Lindsey C. Slaughter; Jasmine Neupane; Haydee E. Laza (Plant and Soil, 2025)
Aims Global peanut production is constrained by the frequency and severity of drought. New insights into photosynthetic biophysical and biochemical limitations under water-deficit stress are important to enhance peanut photosynthetic efficiency and production. This study examines the combined effects of water deficit, genotype, and growth stage on peanut physiology. Methods An experiment was conducted during three growing seasons (2020 – 2022) to evaluate peanut genotypes (AG18, C76-16, GA-09B, and Lariat) at three developmental stages: flowering/peg development ( R 2 -stage ), pod initiation/seed development ( R 4 -stage ), and pod filling/initiation of crop maturity ( R 7 - stage ). The study was carried out under well-watered and water-deficit conditions. We quantified the biophysical (stomatal conductance) and biochemical limitations [the maximum rate of carboxylation ( V c, max ), rate of RuBP regeneration ( J max ), and photosynthetic electron transport rate ( ETR )]. Results The drought-induced reduction in A N during the R 2 -stage stage was primarily attributed to a significant decrease in stomatal conductance ( g s ). In contrast, at the R 7 -stage , the reduction in A N was driven by limitations in the g s , V c, max , and J max . Notably, at the R 7 -stage , genotypes C76-16 and Lariat showed higher g s , ETR , and V c, max , contributing to increased A N and enhanced pod and kernel yield compared to AG18 and GA-09B. Conclusion A N reduction was driven by the biophysical limitation at the R 2 -stage and a combination of biophysical and biochemical limitations at the R 7 -stage. Furthermore, physiological strategies such as maintaining higher stomatal conductance while reducing photosystem II damage, as shown by C76-16, could be an effective drought tolerance strategy for maintaining high pod yield.

Intact glycoconjugates from Taenia crassiceps excreted/secreted products ameliorate chemically induced colitis by modulating inflammation and strengthening adherens junctions - Yadira Ledesma-Soto; Ilse Chávez-Soto; Marissa Calderón-Torres; Andrea Monserrat Rodríguez-Lozoya; Jonadab E. Olguin; Luis B. Hernández-Portilla; César M. Flores-Ortíz; Fernando Candanedo; Miriam Rodriguez-Sosa; Sonia E. Hernández-Navia; Luis I. Terrazas (Inflammopharmacology, 2025)
Background Ulcerative colitis (UC) is a chronic inflammatory disease that is increasing in prevalence worldwide. Notably, helminth infections, known for their immunoregulatory properties, are inversely related to inflammatory conditions such as UC. Research has indicated that Taenia crassiceps infection can improve inflammatory-mediated diseases, including type 1 diabetes, experimental autoimmune encephalomyelitis, and colitis. Subsequent studies revealed that helminth-derived products can replicate the effects of complete infection in the context of inflammatory diseases; however, the mechanisms underlying these effects remain unclear. This study examined the impact of intact glycans from T. crassiceps excreted/secreted products (TcES) on host responses to dextran sodium sulfate (DSS)-induced colitis. Methods UC was induced by administering 4% DSS in the drinking water for 9 days. The mice were treated with intact TcES, glycan-depleted TcES, or protein-depleted TcES 2 days after colitis induction. Symptoms of the disease, along with immunologic and histopathological evaluations, were performed. Results Colitic mice that received intact TcES presented fewer disease symptoms and less histopathological damage. Intact TcES reduced the proinflammatory response while increasing the production of IL-4, IL-22, IL-31, and MCP-1 and promoting M2 macrophage polarization via PD-L2 expression. Furthermore, intact TcES diminished neutrophil infiltration, inhibited NF-κB and p38 phosphorylation in the colon, and suppressed reactive oxygen species and 3-nitrotyrosine levels, thus protecting the colon. These effects were accompanied by increased expression of E-cadherin and β-catenin, indicating improved epithelial barrier integrity. Conversely, mice treated with glycan-depleted or protein-depleted TcES exhibited exacerbated colitis characterized by disruption of colon tissue architecture, extensive inflammation, and epithelial damage, including loss of E-cadherin and β-catenin and a lack of M2 macrophage polarization. Conclusions Glycoconjugates on TcES play a significant role in mediating the immunomodulatory effects that alleviate DSS-induced colitis.

Chloroplast-based molecular markers for discrimination of economically important Vaccinium species - Maura Flynn Gallagher; Felix E. Enciso-Rodriguez; Edson Mario de Andrade Silva; Annette M. Fahrenkrog; Juan Zalapa; Juliana Benevenuto; Karina Lima Reis Borges; Patricio Munoz (Genetic Resources and Crop Evolution, 2025)

Active and passive pathways of nutrient transfer in coral reef ecosystems - Ruth E. Dunn; Nicholas A. J. Graham; Laura-Li Jeannot; Rucha Karkarey; F. Javier Gonzalez-Barrios; Ines D. Lange; Julia Rodriguez Fillol; Ronan Roche; Marleen Stuhr; Cassandra E. Benkwitt (Coral Reefs, 2025)
Coral reefs receive both passive and active nutrient subsidies, supplied via oceanographic processes and animal-mediated transfer, which can bolster reef productivity and resilience to disturbance. We examined the relative importance of these two pathways across lagoonal and seaward reefs, reefs of different depths, and those around islands either with or without breeding seabird colonies using carbon and nitrogen stable isotopes (ð 13 C and ð 15 N) and nutrient metrics (per cent N, %N and carbon-to-nitrogen ratios, C:N). We found increased passive oceanic nutrient inputs in reefs that were both deep and seaward facing, indicated by lower ð 13 C values. Enriched ð 15 N values and lower carbon-to-nitrogen ratios within reefs adjacent to islands with seabird colonies provided evidence of the role of seabirds as active vectors of nutrients to coral reef food webs, particularly within shallow, lagoonal reefs. Though %N values did not seem to provide a good indicator through which to disentangle active vs passive nutrient transport within this context, variation in ð 13 C and ð 15 N values and C:N ratios highlighted the interplay between passive oceanic processes and active seabird contributions to coral reefs. We emphasise the importance of both preserving and restoring natural nutrient pathways, particularly at a time when coral reef ecosystems are under increasing pressure from anthropogenic threats.

Observations of Sargassum carbon influx and biogeochemical impact in La Parguera Marine Reserve - Priscilla N. Molina-Cora; Julio M. Morell; Loraine Martell-Bonet; Luis R. Rodriguez-Matos; Julián E. Morell; Maribel Vélez-Rivera (Frontiers in Marine Science, 2025)
The massive influx of pelagic Sargassum spp. species, also known as Sargassum inundation events (SIEs), first arrived at the Caribbean’s coastal waters in 2011. These events have been linked to hypoxia, among other ecological disturbances. Here, we report data from 2022 on (1) an assessment of the relative magnitude of particulate organic carbon (POC) load arising from SIEs into the La Parguera Marine Reserve (LPMR) basin off the southwest coast of Puerto Rico and (2) the biogeochemical impact of SIE in a nearshore mangrove key within the reserve, Monsio Jose Key Bay (MJKB). Our analysis yields that the carbon influx increased by 20% in the LPMR basin and by 103% in MJKB. Weekly observations of Sargassum input, along with the collection and analysis of water samples in MJKB, evidenced a cause-effect relation between Sargassum carbon loading and frequency of hypoxic (DO < 2 mg·L -1 ) and critically acidic conditions (Aragonite saturation, Ω < 2.0). During the 2022 Sargassum season, hypoxic conditions were detected in 43% of samples collected in MJKB. Considering the modulation of biogeochemical parameters by changes in tide height (Δh) and wind speed (m·s -1 ), stepwise multiple regression analyses (RDA-AIC model selection) showed that significant parameters influencing DO, pH, and Ω include the Sargassum carbon influx and Δh ( p < 0.05). These findings strongly support the hypothesis that the additional input of POC influx enhances microbial mineralization rates responsible for depressed oxygen concentrations and acidic conditions, which could be detrimental to coastal ecosystems. This is particularly concerning in areas prone to SIEs where geomorphological features facilitate the entrainment of floating materials. Proper management requires the identification of vulnerable sites and Sargassum removal. Ongoing efforts towards that goal are underway for LPMR.

Influence of nixtamalization time and solid-state fermentation on masa starch: Morphology, structure, and physicochemical properties - Cecilia Martinez-Ortiz; Oscar Y. Barron-Garcia; Mario E. Rodriguez-Garcia; Eduardo Morales-Sánchez; Mar Villamiel; Marcela Gaytán-Martínez (Innovative Food Science & Emerging Technologies, 2025)

Hydrothermal carbonization of swine manure in a continuous flow reactor pilot plant with process water recycling - R.P. Ipiales; E. Diaz; M.A. de la Rubia; J.J. Rodriguez; A.F. Mohedano (Biomass and Bioenergy, 2025)

Correction: Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Application of a high-density microelectrode array assay using a 3D human iPSC-derived brain microphysiological system model for in vitro neurotoxicity screening of environmental compounds - Kelly E. Carstens; Elena Gronskaya; David Jäckel; Jessica Bertoli; Kelvin Ramirez Cuevas; Julien Dorier; Shan Wang; David Lopez-Rodriguez; Timothy J. Shafer; Marie-Gabrielle Zurich; David Pamies (Archives of Toxicology, 2025)
Unraveling the associations between human exposure to environmental chemicals and potential neurotoxicity presents significant challenges. Evaluation of neurotoxicity potential using animal testing is resource-intensive (financial, labor, and animal use) and faces uncertainties regarding biological relevance to human health outcomes. Therefore, there is a need to develop efficient and human-relevant in vitro new approach methodologies (NAMs) to screen and evaluate chemicals for neurotoxicity potential. Recording of neural network activity using microelectrode array (MEA) technology has been identified as a reliable and reproducible method for evaluating neurotoxicity. Much of this research has been performed in 2D rodent-derived cell models. The ‘BrainSpheres MEA assay’ described in this study offers a promising functional human induced pluripotent stem cell (iPSC)-derived 3D brain model comprising neurons, astrocytes, and oligodendrocytes. We demonstrate consistent spontaneous neuronal firing and network bursting parameters from 7-week-old BrainSpheres using a high-density MEA technology. The performance of this model as a human-relevant NAM was evaluated by conducting a multi-concentration, 13 day exposure study with a set of ten chemicals. Neural activity metrics were assessed and compared to results from a 2D-MEA assay using rodent cells. Loperamide and domoic acid (two assay positive controls) demonstrated similar bioactivity profiles in the BrainSphere MEA assay to the 2D-MEA assay, while acetaminophen (assay negative control) was inactive in both assays. The 2D-MEA model demonstrated more potent bioactivity for 4/7 chemicals that were active in both assays. In the future, reducing replicate variability and testing a larger set of chemicals will likely improve the accuracy and reliability of the assay. These preliminary findings suggest that the BrainSphere assay could be used alongside the rat network formation assay (rNFA) as part of a tiered strategy, where hits in the rNFA are confirmed and further characterized in the BrainSphere model, helping move toward animal-free toxicological testing.

Amino acid and acylcarnitine profile of Aedes aegypti (L) post-blood feeding, after permethrin exposure, and during the life cycle - Mariana Lizbeth Jiménez-Martínez; Gerardo de Jesús Trujillo-Rodriguez; María de Lourdes Ramírez-Ahuja; Olga Karina Villanueva-Segura; Patricio Adrián Zapata-Morin; Griffith Samuel Lizarraga; Laura E. Martinez-de-Villarreal; Margarita L. Martinez-Fierro; Ivan Delgado-Enciso; Jose Ignacio Gonzalez-Rojas; Adriana E. Flores; Antonio Guzman-Velasco; et al. (Insect Biochemistry and Molecular Biology, 2025)

Understanding osmoregulation, cryoprotectant toxicity, and cold tolerance in sea urchin eggs: Implications for cryopreservation - S. Campos; Uxía Rodriguez; J. Troncoso; E. Paredes (Cryobiology, 2025)

Beyond the bite: how mosquito salivary proteins modulate midgut biology and malaria parasite transmission - Thiago Luiz Alves e Silva; Renuka Elizabeth Joseph; Joel Vega-Rodriguez (Current Opinion in Insect Science, 2025)

Biomechanical and Compositional Changes in the Murine Uterus with Age - Mari J. E. Domingo; Triniti N. Vanoven; Raffaella De Vita; Maria E. Florian Rodriguez; Kristin S. Miller; Isaac J. Pence (Annals of Biomedical Engineering, 2025)

Anthocyanin supplementation in adults at risk for dementia: a randomized controlled trial on its cardiometabolic and anti-inflammatory biomarker effects - Miguel German Borda; Robinson Ramírez-Vélez; Felipe Botero-Rodriguez; Jonathan Patricio-Baldera; Chiara de Lucia; Ilaria Pola; George E. Barreto; Khadija Khalifa; Anne Katrine Bergland; Miia Kivipelto; Tommy Cederholm; Henrik Zetterberg; et al. (GeroScience, 2025)
Anthocyanins are dietary flavonoids shown to have a therapeutic capacity to mitigate inflammation and oxidative stress. The present secondary analyses from the “Anthocyanins in People at Risk for Dementia Study” were aimed at (I) determining the intervention’s effect on blood-based markers of cardiovascular disease and inflammation and (II) evaluating whether baseline factors such as age, sex, inflammation, or cardiometabolic score may moderate the intervention’s effect on inflammatory status. This study was an ancillary, 24-week randomized, double-blind, placebo-controlled Phase II trial. Sub-sample participants ( n = 99), aged 60–80 years with mild cognitive impairment or cardiometabolic disorders, were randomized to receive either 320 mg/day of anthocyanins or placebo. The biomarkers analyzed included inflammatory biomarker assessment (IL − 6, IL − 8, IL − 10, IL − 1b, TNF − α, IFN − γ), and C-reactive protein (CRP), as well as albumin, thrombocytes, cholesterol, LDL, HDL, and triglycerides, which were longitudinally compared between both groups. Baseline characteristics were balanced between the groups. ANCOVA analyses reveal 24-week differences favoring the anthocyanin treatment in LDL cholesterol levels (ƞp 2 = 0.078; p = 0.015), cardiometabolic score (ƞp 2 = 0.073; p = 0.021), CRP levels (ƞp 2 = 0.417; p = 0.0001), IL − 6 (ƞp2 = 0.085; p = 0.015), IL − 1b (ƞp 2 = 0.058; p = 0.037), and Inflam z-score 5 (ƞp 2 = 0.059, p = 0.004). Moderation analysis demonstrated that the inflammatory score at baseline was a significant predictor of the effect of the intervention on the CRP levels. Anthocyanin supplementation reduces CRP and cardiovascular disease biomarkers in individuals at risk of dementia, especially when there is increased inflammation at baseline. ClinicalTrials.gov study identifier: NCT03419039.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Limited surface deformation, seismicity, and seismic velocity changes observed in Valles Caldera over decadal timescales - Nathan Maier; Emily E. Rodriguez; Ronni Grapenthin; Andrew Newman; Carly Donahue; Eric Lindsey; Peter Roberts; Savannah Devine (Journal of Volcanology and Geothermal Research, 2025)

Strategic optimization of short-rotation woody crops for bioenergy production - Agustina Anselmino; Frank Piedra-Jimenez; María Analía Rodriguez; Rodolfo G. Dondo; Mariana E. Cóccola (Biomass and Bioenergy, 2025)

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

A novel alternative fate for shrimp fishery wastes as active ingredients in ecofriendly antifouling paints - María V. Laitano; Yamila E. Rodriguez; Guadalupe Rivero; Analía V. Fernández-Gimenez; Guillermo Blustein (Environmental Science and Pollution Research, 2025)

Feed intake, preferences, in vivo digestibility, and nutritional value of tedera (B. bituminosa var. bituminosa) and maralfalfa (Pennisetum purpureum) in Canary sheep - M. Barbera; V. Mendoza-Grimón; J. Espinosa; E. Rodriguez-Ponce; A. Gracia; E. SanJuán; M. R. Ventura (Tropical Animal Health and Production, 2025)
This study evaluated the nutritional value and energy content of tedera ( B. bituminosa var. bituminosa ) and maralfalfa ( Pennisetum purpureum ) through analyses of chemical composition, digestibility, intake, and preference trials. Tedera was compared with maralfalfa and alfalfa hay ( Medicago sativa ). Tedera showed higher crude protein (193 g CP/kg DM) and estimated energy (10.5 MJ DE/kg DM) but lower dry matter (286.3 g DM/kg) and neutral detergent fiber (373 g NDF/kg DM) than both maralfalfa and alfalfa hay. The in vitro organic matter digestibility (IVOMD) of tedera was 61.7%, compared to 51.0% for alfalfa hay and 66.3% for maralfalfa. Digestible organic matter (DOM) ranged from 467 g/kg DM in alfalfa hay to 566.4 g/kg DM in tedera. Four Canary sheep with a mean body weight (BW) of 42.2 ± 5.0 kg were used for digestibility and preference trials. The live weights of the sheep were recorded at the start and end of the 12-day trial. Feed offered and refusals were weighed and recorded daily for eight days, while feces were collected for four days to calculate apparent in vivo digestibility. For tedera, the apparent in vivo OM digestibility, estimated digestible energy, and digestible organic matter were 69.4%, 11.8 MJ/kg DM, and 637.7 g/kg DM, respectively. Preference and feed intake were compared between tedera, maralfalfa and alfalfa hay. Total DM consumption was 1091.3 g/day (tedera + maralfalfa + alfalfa hay), with alfalfa hay intake representing 40.8%, maralfalfa 37.3%, and tedera 21.9% of the total DM consumed. However, no significant differences were observed in the ratio of forages consumed/offered (44.8% for tedera and 51.8% for maralfalfa) or in the total grams of DM, CP, and MJ/kg of DE consumed by the sheep with both forages. The sheep adopted different feeding strategies in response to the chemical composition and nutritive value of the forages. Preferences and intake in this trial were associated with high NDF content in maralfalfa and alfalfa hay and with the high CP content in tedera rather than digestibility results. This may be due to the complementarity of the three forages and the higher CP content in tedera affecting intake. Nevertheless, tedera and marafalfa could be a good forage considering its nutritive value, digestibility, and proven growth performance in herbivores.

Annular solar eclipse effects observed over Mexico on October 14, 2023: A multi-instrument study - M.A. Sergeeva; J.A. Gonzalez-Esparza; O.A. Maltseva; J.H. Castro-Chacon; V.J. Gatica-Acevedo; A. Melgarejo-Morales; I.D. Orrala Legorreta; X. Chiappa; R. Bonifaz; M.E. González-Álvarez; A. Vesnin; P. Corona-Romero; et al. (Advances in Space Research, 2025)

Research updates and progress on nutritional significance of the amides I and II, alpha-helix and beta-sheet ratios, microbial protein synthesis, and steam pressure toasting condition with globar and synchrotron molecular microspectroscopic techniques with chemometrics - Maria E. Rodriguez-Espinosa; Victor H. Guevara-Oquendo; Jiangfeng He; Weixian Zhang; Peiqiang Yu (Critical Reviews in Food Science and Nutrition, 2025)

Promoting Workplace Health, Safety, and Well-Being Among Essential Agricultural Workers Through Vaccine-Preventable Infectious Diseases Training in the Rio Grande Valley - Anabel Rodriguez; David I Douphrate; Ana L Pineda Reyes; Susana Zavala; Andrea V. Cabrera Cruz; Maria D Alegria; Brian Ukaegbu; Annie J Keeney; Brenda Berumen-Flucker; Eva M Shipp; Shannon P Guillot-Wright; Maria E Fernandez-Esquer; et al. (Journal of Agromedicine, 2025)

Age, growth, and reproductive biology of Achilles tang (Acanthurus achilles) around Hawai'i Island, USA - Timothy B. Grabowski; Richard Masse; Dawn McSwain; Annie Larson; Lillian J. Tuttle Raz; Eva Schemmel; Danielle E. Bartz; Nikola Rodriguez (Environmental Biology of Fishes, 2025)

A review of the venom microbiome and its utility in ecology and evolution including future directions for emerging research - Marina E. De León; Eduardo G. P. Fox; Sara Dunaj; Ronald A. Jenner; Carl N. Keiser; Jason Macrander; Samantha A. Nixon; Clarissa J. Nobile; Daniel Petras; Eduardo Rodriguez-Roman; Anthony J. Saviola; Steven A. Trim; et al. (Symbiosis, 2025)

Effect of aging time on the physicochemical properties of lime used to preserve corn postharvest - Efren Herrera-López; Sylvanus Odjo; Luis F. Zubieta-Otero; Brenda L. Contreras-Jiménez; Fabiola Curiel-Ayala; Lina Garcia-Mier; Mario E. Rodriguez-Garcia (Journal of Stored Products Research, 2024)

Taxonomy, systematics and conservation of the highly threatened and endemic Mexican genus Tridimeris (Annonaceae) - Andrés Ernesto Ortiz-Rodriguez; Francis J. Nge; Carlos Rodrigues-Vaz; Vincent Soulé; George E. Schatz; María Fernanda Martínez-Velarde; Leopoldo Hurtado-Reveles; Moises Rangel-Olguin; Thomas L. P. Couvreur (Plant Systematics and Evolution, 2024)
Tridimeris is the only genus of Annonaceae endemic to Mexico, and since its description more than 150 years ago, the genus has been largely ignored. Here, based on herbarium specimens and a comprehensive phylogenomic study involving hundreds of nuclear markers, the first taxonomic revision of the genus Tridimeris (Annonaceae, Malmeioideae, subtribe Sapranthinae) is presented. Ten species are recognized, six of which are newly described here. All the species are exclusively found in Mexico's most humid forests, particularly in the montane cloud forest and the tropical rainforest. The genus Tridimeris is morphologically distinguished from other neotropical genera of the Annonaceae by its leaves with pocket domatia present in the axils of the secondary veins, by its dimerous flowers (two sepals and four petals), basally fused sepals with ciliated margins, by a reduced number of carpels per flower (1–5) and by its large and fleshy fruits (monocarps) with numerous seeds. A highly resolved phylogenetic hypothesis provides strong support for the relationships among Tridimeris species, forming two well-supported clades. Consequently, two new sections are proposed, namely Tridimeris sect. Tridimeris and Tridimeris sect. Zoque . A detailed description of the morphology of the genus is presented, including the description of the pollen, domatia and its phylogenetic relationships. Taxonomic treatments of the species include synonyms, geographic and ecological notes, comparisons with similar species and a preliminary assessment of their conservation status. All species of the genus are potentially threatened with extinction and eight are assessed as Critically Endangered, which makes it the most threatened lineage of Mexican trees. This study emphasizes the importance of scientific collections as invaluable sources of data for current taxonomic revisions and conservation. It is a formal invitation to preserve and support the basic scientific research.

Correction: Long-term antigen-specific immune response by an oncolytic adenovirus encoding SP-SA-E7-4-1BBL in HPV-16 cancer model - Alejandra G. Martinez-Perez; Rodolfo Garza-Morales; Maria J. de Loera-Arias; Sheila A. Villa-Cedillo; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha; Orlando E. Flores-Maldonado; Jesus Valdes; Jose J. Perez-Trujillo; Odila Saucedo-Cardenas (Molecular Biology Reports, 2024)

Long-term antigen-specific immune response by an oncolytic adenovirus encoding SP-SA-E7-4-1BBL in HPV-16 cancer model - Alejandra G. Martinez-Perez; Rodolfo Garza-Morales; Maria de J. Loera-Arias; Sheila A. Villa-Cedillo; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha; Orlando E. Flores-Maldonado; Jesus Valdes; Jose J. Perez-Trujillo; Odila Saucedo-Cardenas (Molecular Biology Reports, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Diastereomers of the Anticancer Peptide CIGB-300 with Altered β-Turn Structures - Celia G. Moya; Rafael Rodriguez; Carlos S. Perez; Hilda Garay; Julian Wiesent; Stefan Gröger; Yordanka Masforrol; Yasser Perera; Silvio E. Perea; Jochen Balbach (International Journal of Peptide Research and Therapeutics, 2024)
Purpose The next-generation anti-tumor drug peptide CIGB-300, developed by the Center for Genetic Engineering and Biotechnology (CIGB), targets casein kinase 2 (CK2) and its substrates, implicating significant therapeutic potential in cancer treatment. A key focus of this study was to compare CIGB-300 and a primary synthetic byproduct, CIGB-300iso, which shares the amino acid sequence with CIGB-300 but was proposed to differ due to racemization. Methods This study explores the synthesis, characterization, and structural elucidation of CIGB-300 and its isomer CIGB-300iso by a comprehensive NMR analysis of seven synthesized diastereomers including amino acid residues C15, H21, and C25. Results This study revealed that CIGB-300iso contains one D enantiomer at position H21. The structures of both isoforms derived from NMR constraints disclosed that the L and D enantiomers have an altered peptide supersecondary structure, with a β-turn type IV 3 found in CIGB-300 and a type I β-turn in CIGB-300iso. Conclusion The configuration of H21 significantly impacts the peptide’s conformations, sidechain orientations and, potentially, its biological activity. These findings highlight the importance of enantiomerically pure peptides for the design and synthesis of drug peptides.

Summarized cereal grain characteristics affecting digestive behavior and nutrient utilization on a quantitative basis: Comparison among oat, hull barley, and hulless barley grain - Marcela R. Tosta; Ganqi Deng; Luciana L. Prates; Ling Yang; Jiangfeng He; Maria E. Rodriguez Espinosa; Hongyu Deng; Weixian Zhang; Xiaogang Yan; Xin Feng; Huihua Zhang; Peiqiang Yu (Journal of Cereal Science, 2024)

Extraction of bio-hydroxyapatite from devilfish (Loricariidae) for the fluoride and cadmium adsorption from water and its feasible photocatalytic properties - Hilda G. Cisneros-Ontiveros; Luis F. Zubieta-Otero; Nahum A. Medellín-Castillo; Alfredo I. Flores-Rojas; Mario E. Rodriguez-Garcia (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Changing How We Talk About DSMES: Creating a Playbook for Programs and Providers - B. Rodriguez; A. Williams; K. Pellechia; J. Bromberg; E. Hanlon (Journal of the Academy of Nutrition and Dietetics, 2024)

A Multicriteria Model for the Assessment of Source Water Contamination by Anthropogenic Activities to Support Land Use Management - Ariane E. Marais; Irène Abi-Zeid; Manuel J. Rodriguez; Roxane Lavoie (Environmental Modeling & Assessment, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Whole-cell biocatalysis for phthalate esters biodegradation in wastewater by a saline soil bacteria SSB-consortium - Marco A. Pereyra-Camacho; Victor E. Balderas-Hernández; Ana P. Barba-de la Rosa; Antonio De Leon-Rodriguez (Chemosphere, 2024)

S16-01 Human exposure to PFAS: what did we learn? Does dose matter? - G. Schoeters; A. Collens; E. Govarts; A. Rodriguez-Carrillo; N. Van Larebeke (Toxicology Letters, 2024)

S13-04 Towards interoperable modelling tools for integrative risk assessment – the PARC model network approach - J. Kruisselbrink; W. de Boer; M. van Lenthe; T. van Voorthuijsen; P. Palmont; L. Rodriguez Martin; D. Devriendt; E. Govarts; M. Carsique; A. Crépet; J. van Klaveren; J. Engel (Toxicology Letters, 2024)

Exploring the influence of wood ash, maize cob ash, and tequesquite (alkaline rock) on nixtamalization of maize - Gricelda Vázquez-Carrillo; Leticia García-Cruz; Aide Molina-Macedo; María de la Luz Marrufo-Diaz; Mario E. Rodriguez-Garcia; Rafael Mier-Sainz Trapaga; Charles Bett; Natalia Palacios-Rojas (International Journal of Gastronomy and Food Science, 2024)

A multi-technique approach to unveil the composition and fabrication of a pre-Roman glass masterpiece: a double-faced human-head shape polychrome glass pendant (2nd -1st c. BC) - S. Barroso-Solares; E. Estalayo; J. Aramendia; E. Rodriguez-Gutierrez; C. Sanz-Minguez; A. C. Prieto; J. M. Madariaga; J. Pinto (Archaeological and Anthropological Sciences, 2024)
Pre-Roman glass craftsmanship reached its summit with the development of complex polychrome glass beads, being the Phoenician glass pendants the most exquisite and elaborate example. The uniqueness and complexity of such findings could reveal key information for the understanding of the production and trade of glass pieces at that age. However, these findings have practically never been studied from a physic-chemical perspective. In this work, a remarkable polychrome glass pendant (2nd -1st c. BC) found at the archaeological site of Pintia (Padilla de Duero, Valladolid, Spain) is studied by a multi-analytical non-destructive approach, employing X-ray tomography to understand its fabrication procedure, as well as X-ray fluorescence (XRF) and Raman spectroscopy, both employed in microscopic mode, to determine the composition of each glass employed in its fabrication. The outstanding preservation state and well-defined archaeological context of this glass pendant offered a unique opportunity to expand the understanding of pre-Roman glass pieces, while the combination of the experimental techniques employed provided the first complete and detailed study of a Phoenician glass pendant. The fabrication procedure of the pendant has been identified step-by-step, showing evidence of the use of pre-made pieces for the eyes, as well as hints of its fabrication in a secondary workshop. Moreover, the microchemical analysis of the vividly colored glasses by XRF and Raman spectroscopy revealed a composition compatible with the use of natron as fluxing agent, typical of Phoenician glass, the presence of surface alterations corresponding to carbonatation processes, as well as the nature of the employed chromophores or pigments: Mn, Cu, and Co for the blue, Fe-S for the black, CaSb 2 O 7 and CaSb 2 O 7 + TiO 2 for two diverse white glasses, and a pyrochloric triple oxide (Pb 2 Sb 2 − x Sn x O 7−x/2 ) and lead oxides for the yellow. Remarkably, the use of pyrochloric triple oxides as yellow pigments has scarcely been previously reported at that age. Finally, the identification by Raman spectroscopy of CaSb 2 O 7 and the β-phase of CaSiO 3 , as well as the Raman spectra features of the glass matrix corresponding to the blue glass, indicated maximum firing temperatures below 1100 °C.

“Hg distribution and accumulation in soil and vegetation in areas impacted by artisanal gold mining in the Southern Amazonian region of Madre de Dios, Peru.” - Maria J. Rodriguez-Pascual; Claudia M. Vega; Natasha Andrade; Luis E. Fernández; Miles R. Silman; Alba Torrents (Chemosphere, 2024)

"Effects of floating aquatic vegetation and canal sediment on phosphorus in drainage discharges in agricultural canals: A case study in the everglades agricultural area, Florida" - Mohsen Tootoonchi; Anne E. Sexton; Jennifer A. Cooper; Andres F. Rodriguez; Maryory Orton; Timothy A. Lang; Samira H. Daroub (Water Research, 2024)

Improving physiological simulations in seasonally dry tropical forests with limited measurements - Iago Alvarenga e Silva; Daniel Andres Rodriguez; Rogério Pinto Espíndola (Theoretical and Applied Climatology, 2024)

Spatio-temporal patterns in the biomass, species composition and nitrogen content of drift macroalgae in an urbanised coastal embayment - Juan Manuel Valero-Rodriguez; Tim Dempster; Wei Wen Wong; John A. Lewis; Perran L. M. Cook; Stephen E. Swearer (Journal of Applied Phycology, 2024)
Understanding spatio-temporal variability in the production of drift macroalgae is useful for monitoring and assessing the influence of local anthropogenic nutrient sources on coastal ecosystems. In this study we: (1) assessed how the drift macroalgal community composition and biomass have changed over a 22-year period in Port Phillip Bay (a large coastal embayment in Victoria, Australia); and (2) measured the amount of accumulated nitrogen in drift macroalgae and the contribution of anthropogenic nitrogen sources through isotopic analysis. The surveys revealed little overlap in species composition (<13%) and a significant decrease in standing stock biomass (from 631 to 49 g m -2 ) between surveys (1995/1996 and 2017/2018). This was associated with a high degree of turnover (β-diversity) at the genus level between surveys (mean – 0.53), resulting in distinct communities at all sites, particularly among red algal genera. In addition, the occurrence of ephemeral macroalgal blooms and a semi-perennial mat of the red macroalga Botryocladia sonderi at 10-15 m depth at locations close to nutrient sources indicate drift macroalgae are important nutrient accumulators in the bay. Isotopic analysis revealed a high contribution of anthropogenic-derived nitrogen (δ 15 N > 17‰ and ~ 3% N content) at depths and locations close to nutrient sources, particularly at times of the year when large wastewater discharges occur. Harvesting of drift macroalgae could be a cost-effective solution for offsetting nitrogen inputs from anthropogenic sources, but it will be important to first investigate whether harvesting results in negative impacts to associated fauna or nutrient cycling.

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Sediment analysis and water quality assessment in the Pixquiac basin: drinking water supply of Xalapa city (Veracruz, Mexico) - M. C. Dupont; E. Martinez-Tavera; P. F. Rodriguez-Espinosa; A. G. Hernandez-Ramirez; P. Guadarrama Guzmán (Environmental Monitoring and Assessment, 2024)

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Total CO2 budget estimate and degassing dynamics for an active stratovolcano: Turrialba Volcano, Costa Rica - Kate M. Nelson; Christofer Jiménez; Chad D. Deering; Maarten J. de Moor; Joshua M. Blackstock; Stephen P. Broccardo; Florian M. Schwandner; Joshua B. Fisher; Snehamoy Chatterjee; Guillermo Alvarado Induni; Alejandro Rodriguez; Doménicca Guillén Pachacama; et al. (Journal of Volcanology and Geothermal Research, 2024)

Graphene-based Semiconductors for Photocatalytic Degradation of Organic Dye from Wastewater: A Comprehensive Review - Pierre G. Ramos; Harry Rivera; Luis A. Sánchez; María E. Quintana; Juan M. Rodriguez (Water, Air, & Soil Pollution, 2024)

Exploring genomic inbreeding and selection signatures in a commercial Brangus herd through functional annotation - Gabriel A. Zayas; Eduardo E. Rodriguez; Aakilah S. Hernandez; Fernanda M. Rezende; Raluca G. Mateescu (Journal of Applied Genetics, 2024)

Development and growth of bovine calves demi-embryos - Amada E. Ynsaurralde-Rivolta; Andres Rogberg-Muñoz; Sebastian Lopez-Valiente; Sebastian Maresca; Alejandro Rodriguez; Carlos Munar; Sebastian Munilla-Leguizamón; Franco A. Dellavalle; Daniel Salamone (Animal Reproduction Science, 2024)

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Metal accumulation in salt marsh soils along the East Coast of the United States - Kristen E. Jezycki; Elise Rodriguez; Christopher B. Craft; Scott C. Neubauer; James T. Morris; Steven T. Goldsmith; Peleg Kremer; Nathaniel B. Weston (Science of The Total Environment, 2024)

Trophic ecology of sympatric sea turtles in the tropical Atlantic coast of Brazil - Moises F. Bezerra; Cesar A. Barrios-Rodriguez; Carlos E. Rezende; Melania C. López-Castro; Luiz D. Lacerda (Marine Environmental Research, 2024)

Evaluation of water diffusion, water vapor permeability coefficients, physicochemical and antimicrobial properties of thin films of nopal mucilage, orange essential oil, and orange pectin - Roberta M. Mora-Palma; Porfirio E. Martinez-Munoz; Margarita Contreras-Padilla; A. Feregrino-Perez; Mario E. Rodriguez-Garcia (Journal of Food Engineering, 2024)

Granulomatous pneumonia caused by Mycobacterium simiae and necroulcerative enteritis caused by Entamoeba spp in a panther chameleon (Furcifer pardalis) - E. Martínez Fuentes; J.T. Pico Rodriguez; A. Reyes Matute; L.C. Martínez Chavarria (Journal of Comparative Pathology, 2024)

Pathological and transcript analysis of protection induced by MTBVAC and BCG against Mycobacterium tuberculosis infection in rhesus macaques - F.J. Salguero; J. Medley; L. Hunter; I. Ruedas-Torres; A. Bird; E. Puentes; E. Rodriguez; S.J. Waddell; C. Martin; S. Sharpe (Journal of Comparative Pathology, 2024)

An updated catalog of IPS radio sources observed by MEXART at 140 MHz for space weather studies - G. Baron; E. Aguilar-Rodriguez; J.C. Mejia-Ambriz; O. Chang; J.A. Gonzalez-Esparza; P. Villanueva; E. Andrade (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Combined and sequential exposure to prenatal second hand smoke and postnatal maternal distress is associated with cingulo-opercular global efficiency and attention problems in school-age children - Paige B. Greenwood; Mariah DeSerisy; Emily Koe; Elizabeth Rodriguez; Leilani Salas; Frederica P. Perera; Julie Herbstman; David Pagliaccio; Amy E. Margolis (Neurotoxicology and Teratology, 2024)

Holocene organic matter composition in relation to relative sea level stands and associated morphometric changes of a lagoonal system - V. Carvalho; L. Gonzalez; C. Bueno; C. Segura; S.R. Bottezini; A. Leonhardt; D. Diniz; P. Dentzien-Dias; L. Perez; H. Evangelista; M.V. Licínio; H. Inda; et al. (Marine Geology, 2024)

Photochemical fate of quaternary ammonium compounds (QACs) and degradation pathways prediction through computational analysis - Sanjeeb Mohapatra; Jovina Lew Li Xian; Andy Galvez-Rodriguez; Onkar Sudhir Ekande; Jörg E. Drewes; Karina Yew-Hoong Gin (Journal of Hazardous Materials, 2024)

One hundred and six years of change in a S onoran D esert plant community: Impact of climate anomalies and trends in species sensitivities - Charlotte Brown; Susana Rodriguez Buritica; Deborah E. Goldberg; Frank Reichenbacher; D. Lawrence Venable; Robert H. Webb; Benjamin T. Wilder (Ecology, 2024)
A major restriction in predicting plant community response to future climate change is a lack of long‐term data needed to properly assess species and community response to climate and identify a baseline to detect climate anomalies. Here, we use a 106‐year dataset on a Sonoran Desert plant community to test the role of extreme temperature and precipitation anomalies on community dynamics at the decadal scale and over time. Additionally, we tested the climate sensitivity of 39 desert plant species and whether sensitivity was associated with growth form, longevity, geographic range, or local dominance. We found that desert plant communities had shifted directionally over the 106 years, but the climate had little influence on this directional change primarily due to nonlinear shifts in precipitation anomalies. Decadal‐scale climate had the largest impact on species richness, species relative density, and total plant cover, explaining up to 26%, 45%, and 55% of the variance in each, respectively. Drought and the interaction between the frequency of freeze events and above‐average summer precipitation were among the most influential climate factors. Increased drought frequency and wetter periods with frequent freeze events led to larger reductions in total plant cover, species richness, and the relative densities of dominant subshrubs Ambrosia deltoidea and Encelia farinosa . More than 80% of the tested species were sensitive to climate, but sensitivity was not associated with a species' local dominance, longevity, geographic range, or growth form. Some species appear to exhibit demographic buffering, where when they have a higher sensitivity to drought, they also tend to have a higher sensitivity to favorable (i.e., wetter and hotter) conditions. Overall, our results suggest that, while decadal‐scale climate variation substantially impacts these desert plant communities, directional change in temperature over the last century has had little impact due to the relative importance of precipitation and drought. With projections of increased drought in this region, we may see reductions in total vegetation cover and species richness due to the loss of species, possibly through a breakdown in their ability to demographically buffer climatic variation, potentially changing community dynamics through a change in facilitative and competitive processes.

Exploring fishery waste potential as antifouling component - Juliana Lenchours Pezzano; Yamila E. Rodriguez; Analía V. Fernández-Gimenez; María V. Laitano (Environmental Science and Pollution Research, 2024)

A solar evaporator fabricated from corncob waste for the desalination of seawater and removal of oil/herbicides from contaminated water - E. Valadez-Renteria; J. Oliva; A.I. Oliva; M.A. Ruiz-Gomez; A. Encinas; V. Rodriguez-Gonzalez (Chemosphere, 2024)

Unveiling Sticholysin II and plasmid DNA interaction: Implications for developing non-viral vectors - Felipe A. Escalona-Rodriguez; Yoelys Cruz-Leal; Javier La O-Bonet; Julio A. Pérez-Erviti; Mario Ernesto Valdés-Tresanco; Ada L. Rivero-Hernández; Maricary Sifontes-Niebla; Alexis Manso-Vargas; Belinda Sánchez; Carlos Alvarez; Leandro R.S. Barbosa; Rosangela Itri; et al. (Toxicon, 2024)

Conjugation of lesser mealworm (Alphitobius diaperinus) larvae protein with polyphenols for the development of innovative antioxidant emulsifiers - Aurélie Ballon; Maria-Paz Romero; Luis E. Rodriguez-Saona; Sílvia de Lamo-Castellví; Carme Güell; Montserrat Ferrando (Food Chemistry, 2024)

Effect of biosolid compost amended on Pb availability in soils cultivated with lettuce - M. E. Gómez; G. V. Ferreyroa; M. J. Salazar; M. L. Pignata; J. H. Rodriguez (International Journal of Environmental Science and Technology, 2024)

Exploring the potential of microbial fuel cell-assisted biodegradation of nonylphenol - E. De la Peña; C. Castillo-Zacarías; R. G. Araújo; M. Rostro-Alanis; R. Parra-Saldivar; J. Rodriguez-Rodriguez (International Journal of Environmental Science and Technology, 2024)

Nativity differences in socioeconomic barriers and healthcare delays among cancer survivors in the All of Us cohort - Angel Arizpe; Stephanie Navarro; Carol Y. Ochoa-Dominguez; Claudia Rodriguez; Sue E. Kim; Albert J. Farias (Cancer Causes & Control, 2024)
Purpose We aimed to assess whether nativity differences in socioeconomic (SES) barriers and health literacy were associated with healthcare delays among US cancer survivors. Methods “All of Us” survey data were analyzed among adult participants ever diagnosed with cancer. A binary measure of healthcare delay (1+ delays versus no delays) was created. Health literacy was assessed using the Brief Health Literacy Screen. A composite measure of SES barriers (education, employment, housing, income, and insurance statuses) was created as 0, 1, 2, or 3+. Multivariable logistic regression model tested the associations of (1) SES barriers and health literacy with healthcare delays, and (2) whether nativity modified this relationship. Results Median participant age was 64 years ( n = 10,020), with 8% foreign-born and 18% ethnic minorities. Compared to survivors with no SES barriers, those with 3+ had higher likelihood of experiencing healthcare delays (OR 2.18, 95% CI 1.84, 2.58). For every additional barrier, the odds of healthcare delays were greater among foreign-born (1.72, 1.43, 2.08) than US-born (1.27, 1.21, 1.34). For every 1-unit increase in health literacy among US-born, the odds of healthcare delay decreased by 9% (0.91, 0.89, 0.94). Conclusion We found that SES barriers to healthcare delays have a greater impact among foreign-born than US-born cancer survivors. Higher health literacy may mitigate healthcare delays among US cancer survivors. Healthcare providers, systems and policymakers should assess and address social determinants of health and promote health literacy as a way to minimize healthcare delays among both foreign- and US-born cancer survivors.

Analysis of an optical imaging system prototype for autonomously monitoring zooplankton in an aquaculture facility - M.N. Bowman; R.A. McManamay; A. Rodriguez Perez; G. Hamerly; W. Arnold; E. Steimle; K. Kramer; B. Norris; D. Prangnell; M. Matthews (Aquacultural Engineering, 2024)

Effects of meteo-oceanographic conditions on the weathering processes of oil spills in northeastern Brazil - Humberto L. Varona; Carlos Noriega; Amilcar E. Calzada; Carmen Medeiros; Alexander Lobaina; Alejandro Rodriguez; Dayron Chang; Dailin Reyes; Julia Araujo; Marcus Silva; Marcio das Chagas Moura; Moacyr Araujo (Marine Pollution Bulletin, 2024)

Are remote rural areas in Europe remarkable? Challenges and opportunities - Carolina Perpiña Castillo; Ricardo Ribeiro Barranco; Riccardo Curtale; Mert Kompil; Chris Jacobs-Crisioni; Sara Vallecillo Rodriguez; Jean-Philippe Aurambout; Filipe Batista e Silva; Patrizia Sulis; Davide Auteri (Journal of Rural Studies, 2024)

Inverse priority effects: A role for historical contingency during species losses - Agostina Torres; Sara E. Kuebbing; Katharine L. Stuble; Samantha A. Catella; Martín A. Núñez; Mariano A. Rodriguez‐Cabal (Ecology Letters, 2024)
Communities worldwide are losing multiple species at an unprecedented rate, but how communities reassemble after these losses is often an open question. It is well established that the order and timing of species arrival during community assembly shapes forthcoming community composition and function. Yet, whether the order and timing of species losses can lead to divergent community trajectories remains largely unexplored. Here, we propose a novel framework that sets testable hypotheses on the effects of the order and timing of species losses— inverse priority effects —and suggests its integration into the study of community assembly. We propose that the order and timing of species losses within a community can generate alternative reassembly trajectories, and suggest mechanisms that may underlie these inverse priority effects. To formalize these concepts quantitatively, we used a three‐species Lotka‐Volterra competition model, enabling to investigate conditions in which the order of species losses can lead to divergent reassembly trajectories. The inverse priority effects framework proposed here promotes the systematic study of the dynamics of species losses from ecological communities, ultimately aimed to better understand community reassembly and guide management decisions in light of rapid global change.

Current deformation along the northern Caribbean plate boundary from GNSS measurements in Cuba - E. Calais; O.F. Gonzalez; E.D. Arango-Arias; B. Moreno; R. Palau; M. Cutie; E. Diez; C. Montenegro; E. Rodriguez Roche; J. Garcia; E. Castellanos; S. Symithe (Tectonophysics, 2023)

Monitoring long-term vegetation condition dynamics in persistent semi-arid wetland communities using time series of Landsat data - Li Wen; Tanya J. Mason; Shawn Ryan; Joanne E. Ling; Neil Saintilan; Jose Rodriguez (Science of The Total Environment, 2023)

Native plant growth promoting rhizobacteria improve the growth of pepper seedlings and modify the phenolic compounds profile - M. Andrés Lobato-Ureche; Marí. Micaela Pérez-Rodriguez; E. Malovini; P.N. Piccoli; R.P. Monasterio; A. Carmen Cohen (Rhizosphere, 2023)

Pharmacological inhibition of plasminogen activator inhibitor-1 prevents memory deficits and reduces neuropathology in APP/PS1 mice - Guadalupe Rodriguez; Mesut Eren; Isabel Haupfear; Kirsten L. Viola; Erika N. Cline; Toshio Miyata; William L. Klein; Douglas E. Vaughan; Hongxin Dong (Psychopharmacology, 2023)

Pollen DNA metabarcoding reveals cryptic diversity and high spatial turnover in alpine plant–pollinator networks - Francisco Encinas‐Viso; Jessica Bovill; David E. Albrecht; Jaime Florez‐Fernandez; Bryan Lessard; James Lumbers; Juanita Rodriguez; Alexander Schmidt‐Lebuhn; Andreas Zwick; Liz Milla (Molecular Ecology, 2023)
Alpine plant–pollinator communities play an important role in the functioning of alpine ecosystems, which are highly threatened by climate change. However, we still have a poor understanding of how environmental factors and spatiotemporal variability shape these communities. Here, we investigate what drives structure and beta diversity in a plant–pollinator metacommunity from the Australian alpine region using two approaches: pollen DNA metabarcoding (MB) and observations. Individual pollinators often carry pollen from multiple plant species, and therefore we expected MB to reveal a more diverse and complex network structure. We used two gene regions (ITS2 and trnL ) to identify plant species present in the pollen loads of 154 insect pollinator specimens from three alpine habitats and construct MB networks, and compared them to networks based on observations alone. We compared species and interaction turnover across space for both types of networks, and evaluated their differences for plant phylogenetic diversity and beta diversity. We found significant structural differences between the two types of networks; notably, MB networks were much less specialized but more diverse than observation networks, with MB detecting many cryptic plant species. Both approaches revealed that alpine pollination networks are very generalized, but we estimated a high spatial turnover of plant species (0.79) and interaction rewiring (0.6) as well as high plant phylogenetic diversity (0.68) driven by habitat differences based on the larger diversity of plant species and species interactions detected with MB. Overall, our findings show that habitat and microclimatic heterogeneity drives diversity and fine‐scale spatial turnover of alpine plant–pollinator networks.

Bokashi fermentation of brewery’s spent grains positively affects larval performance of the black soldier fly Hermetia illucens while reducing gaseous nitrogen losses - Marco Gebiola; Michael V. Rodriguez; Alexandro Garcia; Andrea Garnica; Jeffery K. Tomberlin; Francesca M. Hopkins; Kerry E. Mauck (Waste Management, 2023)

Human milk: From complex tailored nutrition to bioactive impact on child cognition and behavior - Carolina de Weerth; Anna-Katariina Aatsinki; Meghan B. Azad; Frank F. Bartol; Lars Bode; Maria Carmen Collado; Amanda M. Dettmer; Catherine J. Field; Meagan Guilfoyle; Katie Hinde; Aniko Korosi; Hellen Lustermans; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Identifying pollution dynamics using discrete Fourier transform: From an urban-rural river, Central Mexico - P.F. Rodriguez-Espinosa; Jorge Fonseca-Campos; K.M. Ochoa-Guerrero; A.G. Hernandez-Ramirez; J. Tabla-Hernandez; E. Martínez-Tavera; E. Lopez-Martínez; M.P. Jonathan (Journal of Environmental Management, 2023)

Kinetics of Na- and K- uranyl arsenate dissolution - Isabel Meza; Noah Jemison; Jorge Gonzalez-Estrella; Peter C. Burns; Virginia Rodriguez; Ginger E. Sigmon; Jennifer E.S. Szymanowski; Abdul-Mehdi S. Ali; Kaelin Gagnon; José M. Cerrato; Peter Lichtner (Chemical Geology, 2023)

Cu(II)-acylhydrazone complex, a potent and selective antitumor agent against human osteosarcoma: Mechanism of action studies over in vitro and in vivo models - Lucia M. Balsa; Luisina M. Solernó; Maria R. Rodriguez; Beatriz S. Parajón-Costa; Ana C. Gonzalez-Baró; Daniel F. Alonso; Juan Garona; Ignacio E. León (Chemico-Biological Interactions, 2023)

LP-51: Determining of a broad range of organic chemicals in seminal plasma through an innovative LC-HRMS-based methodology suitable for target and non-target analysis - E. Sánchez-Resino; M. Marquès; D. Gutiérrez-Martín; E. Restrepo-Montes; M. Á. Martínez-Rodriguez; A. Salas-Huetos; N. Babio; J. Salas-Salvadó; J.L. Domingo; R. Gil-Solsona; P. Gago-Ferrero (Toxicology Letters, 2023)

P21-14: Neurodevelopmental toxicity of T-2 mycotoxin in human-based primary and induced pluripotent stem cell-derived neural progenitor cells in 3D and 2D - M. Taroncher Ruiz; J. Kapr; K. Bartmann; J. Tigges; Y. Rodriguez-Carrasco; M.J. Ruiz; E. Fritsche (Toxicology Letters, 2023)

P21-05: Neurotoxicity/neuroactivity profiling in zebrafish in larvae using a battery of high-content locomotor activity arrays - A.M. Frías; E. Georgilis; A. Arbelaiz; C. Santos; A. Muriana; C. Rodriguez; A. Del Pozo; B. Molina (Toxicology Letters, 2023)

S17-02: The Long-term Impact of Perinatal Exposures on Susceptibility to Immune-mediated Diseases - K.A. Rychlik; E.J. Illingworth; S.E. Attreed; S.S. Sanchez; A. Grant-Alfieri; M.C. Rodriguez Steube; A. Mathur; I.F. Sanchez; C. Tang; M. Suresh; G. Lopez-Cecetaite; P. Sadhukhan; et al. (Toxicology Letters, 2023)

S01-03: PFAS exposure among European teenagers included in the HBM4EU-Aligned studies and its relationship with reproductive hormone and Kisspeptin levels - M.F. Fernández; A. Rodriguez-Carrillo; S. Pedraza; E. den Hond; L. Fábelová; S. Remy; G. Schoeters (Toxicology Letters, 2023)

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

In vitro bioassays to monitor complex chemical mixtures at a carbon-based indirect potable reuse plant - Enrique E. Rodriguez; Charles B. Bott; Krista R. Wigginton; Nancy G. Love (Water Research, 2023)

Correction: Nectins and Nectin-like molecules drive vascular development and barrier function - Doryssa Hermans; Carla Rodriguez-Mogeda; Hannelore Kemps; Annelies Bronckaers; Helga E. de Vries; Bieke Broux (Angiogenesis, 2023)

Nectins and Nectin-like molecules drive vascular development and barrier function - Doryssa Hermans; Carla Rodriguez-Mogeda; Hannelore Kemps; Annelies Bronckaers; Helga E. de Vries; Bieke Broux (Angiogenesis, 2023)

Use-up day and flexible recipes: Reducing household food waste by helping families prepare food they already have - A. Cooper; R. Lion; O.E. Rodriguez-Sierra; P. Jeffrey; D. Thomson; K. Peters; L. Christopher; M.J.H. Zhu; L. Wistrand; P. van der Werf; E. van Herpen (Resources, Conservation and Recycling, 2023)

Correction to: Prey size spectra and predator to prey size ratios of southern ocean salps - Christian K. Fender; Moira Décima; Andres Gutierrez‑Rodriguez; Karen E. Selph; Natalia Yingling; Michael R. Stukel (Marine Biology, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Effect of the incident wind angle in a frigate with Coanda active flow control - J.C. Matías; R. Bardera; E. Barroso; A. Rodriguez-Sevillano (Ocean Engineering, 2023)

Contribution of TGFß and of a cocktail of TGFß and the pro-inflammatory cytokines IL-1, IL- 6 and TNFα to the establishment of a fibrotic phenotype in endometrial fibroblasts of mares - Yat S. Wong; Pamela Poblete; Lidice Mendez; Ana C. Mancanares; Lleretny Rodriguez-Alvarez; Fernando E. Saravia; Fidel O. Castro (Journal of Equine Veterinary Science, 2023)

Effect of intra-uterine infusion of prostaglandin E1 on equine serum level and intra-ovulatory interval - Claire E Card; Mariana Diel de Amorim; Mike Byron; Julia Quental-Caribe; Maria F Lopez-Rodriguez (Journal of Equine Veterinary Science, 2023)

Embryo biopsy and vitrification applied to a commercial embryo transfer program in Argentina - Fernando L Riera; Jaime E Roldán; Maria B Rodriguez; Fernando A Jastrzebski; Monique Lopez Echeverria; Katrin Hinrichs (Journal of Equine Veterinary Science, 2023)

Highly efficient adsorption of furosemide drug by using a Ce0.8Sm0.15Nd0.05O2-δ compound immobilized on massively wasted single use packets - E. Valadez-Renteria; J. Oliva; K.P. Padmasree; A.I. Oliva; V. Rodriguez-Gonzalez (Journal of Environmental Chemical Engineering, 2023)

Environmental controls on the hydrogen isotopic composition of volcanic glass from the Southern Afar rift, eastern Ethiopia - Sebastian Jimenez-Rodriguez; Jay Quade; Naomi E. Levin; Christopher J. Campisano; Gary E. Stinchcomb; Diana C. Roman; Zelalem Bedaso (Chemical Geology, 2023)

A case of feline osteochondromatosis - Á. Gómez; A. Rodriguez Largo; E. Pérez; P. Mendivil; S. Loomans; M. Pérez; K. Chiers; L. Luján (Journal of Comparative Pathology, 2023)

Study of morphological, structural, pasting, thermal, and vibrational changes in maize and isolated maize starch during germination - María G. Nieves-Hernández; Brenda L. Correa-Piña; Edgar A. Esquivel-Fajardo; Oscar Y. Barrón-García; Marcela Gaytán-Martínez; Mario E. Rodriguez-Garcia (Journal of Cereal Science, 2023)

Protein recovery from brewery solid wastes - Luciana M. Rodriguez; Julia L. Camina; Virginia Borroni; Ethel E. Pérez (Food Chemistry, 2023)

Scalable Query Answering Under Uncertainty to Neuroscientific Ontological Knowledge: The NeuroLang Approach - Gaston E. Zanitti; Yamil Soto; Valentin Iovene; Maria Vanina Martinez; Ricardo O. Rodriguez; Gerardo I. Simari; Demian Wassermann (Neuroinformatics, 2023)

Elastomeric biodegradable starch/bentonite nanocomposites. Structure-thermo-mechanical correlation and degradation behavior - A. Romo-Uribe; A. Reyes-Mayer; M. Calixto-Rodriguez; E. Sarmiento-Bustos (Carbohydrate Polymers, 2023)

Holistic Assessment of Calcium Fertilization in Potato: Diagnostic, Productivity, and Tuber Quality - C. M. Giletto; M. Kloster Erreguerrena; P. Ceroli; W. Carciochi; S. E. Silva; S. Rodriguez; F. Salvagiotti; N. I. Reussi Calvo (Journal of Soil Science and Plant Nutrition, 2023)

A Retrospective Review of Center for Biologics Evaluation and Research Advisory Committee Meetings in the Context of the FDA’s Benefit-Risk Framework - Jane Namangolwa Mutanga; Ujwani Nukala; Marisabel Rodriguez Messan; Osman N. Yogurtcu; Quinn McCormick; Zuben E. Sauna; Barbee I. Whitaker; Richard A. Forshee; Hong Yang (The AAPS Journal, 2023)

PFAS levels and exposure determinants in sensitive population groups - L. Fábelová; A. Beneito; M. Casas; A. Colles; L. Dalsager; E. Den Hond; C. Dereumeaux; K. Ferguson; L. Gilles; E. Govarts; A. Irizar; M.J. Lopez Espinosa; et al. (Chemosphere, 2023)

Adapting to climate change on desert rangelands: A multi-site comparison of grazing behavior plasticity of heritage and improved beef cattle - Andres F. Cibils; Rick E. Estell; Sheri Spiegal; Shelemia Nyamuryekung'e; Matthew M. McIntosh; Danielle M. Duni; Oscar A. Herrera Conegliano; Felipe A. Rodriguez Almeida; Octavio Roacho Estrada; Lisandro J. Blanco; Michael C. Duniway; Santiago A. Utsumi; et al. (Journal of Arid Environments, 2023)

Statistical Analysis and Assessment of Water Quality Parameters in Relation to the Use of Algae as Bioindicators in Contaminated Reservoirs - A. Guerrero Aguilar; C. Schüth; U. E. Rodriguez Castrejon; B. Noriega Luna; A. H. Serafin Muñoz (Water, Air, & Soil Pollution, 2023)

Serotonin transporter availability in physically aggressive personality disordered patients: associations with trait and state aggression, and response to fluoxetine - Daniel R. Rosell; Mark Slifstein; Judy Thompson; Xiaoyan Xu; M. Mercedes Perez-Rodriguez; Margaret M. McClure; Erin A. Hazlett; Antonia S. New; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; Larry S. Siever; et al. (Psychopharmacology, 2023)

Characterization of the molecular mechanisms of silicon uptake in coccolithophores - Sarah Ratcliffe; Erin M. Meyer; Charlotte E. Walker; Michael Knight; Heather M. McNair; Paul G. Matson; Debora Iglesias‐Rodriguez; Mark Brzezinski; Gerald Langer; Aleksey Sadekov; Mervyn Greaves; Colin Brownlee; et al. (Environmental Microbiology, 2023)
Coccolithophores are an important group of calcifying marine phytoplankton. Although coccolithophores are not silicified, some species exhibit a requirement for Si in the calcification process. These species also possess a novel protein (SITL) that resembles the SIT family of Si transporters found in diatoms. However, the nature of Si transport in coccolithophores is not yet known, making it difficult to determine the wider role of Si in coccolithophore biology. Here, we show that coccolithophore SITLs act as Na + ‐coupled Si transporters when expressed in heterologous systems and exhibit similar characteristics to diatom SITs. We find that CbSITL from Coccolithus braarudii is transcriptionally regulated by Si availability and is expressed in environmental coccolithophore populations. However, the Si requirement of C. braarudii and other coccolithophores is very low, with transport rates of exogenous Si below the level of detection in sensitive assays of Si transport. As coccoliths contain only low levels of Si, we propose that Si acts to support the calcification process, rather than forming a structural component of the coccolith itself. Si is therefore acting as a micronutrient in coccolithophores and natural populations are only likely to experience Si limitation in circumstances where dissolved silicon (DSi) is depleted to extreme levels.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Bioprospection of naturalized soybean-nodulating Bradyrhizobium strains in Uruguayan soils: a genetic and symbiotic approach - N. E. Rodriguez Rodriguez; E. Beyhaut; M. Sicardi; A. Rodríguez-Blanco (Environmental Sustainability, 2023)

Detecting volunteer cotton plants in a corn field with deep learning on UAV remote-sensing imagery - Pappu Kumar Yadav; J. Alex Thomasson; Robert Hardin; Stephen W. Searcy; Ulisses Braga-Neto; Sorin C. Popescu; Daniel E Martin; Roberto Rodriguez; Karem Meza; Juan Enciso; Jorge Solorzano Diaz; Tianyi Wang (Computers and Electronics in Agriculture, 2023)

Derelict gear from an illegal fishery: Lessons from gear retrieval efforts in the Upper Gulf of California - E. Aceves-Bueno; L. Davids; J.A. Rodriguez-Valencia; A.M. Jaramillo-Legorreta; E. Nieto-Garcia; G. Cárdenas-Hinojosa; E. Hidalgo-Pla; A. Bonilla-Garzón; A.J. Diaz-de-Leon; L. Rojas-Bracho; M.A. Cisneros-Mata (Marine Policy, 2023)

PFAS levels and determinants of variability in exposure in European teenagers – Results from the HBM4EU aligned studies (2014–2021) - D. Richterová; E. Govarts; L. Fábelová; K. Rausová; L. Rodriguez Martin; L. Gilles; S. Remy; A. Colles; L. Rambaud; M. Riou; C. Gabriel; D. Sarigiannis; et al. (International Journal of Hygiene and Environmental Health, 2023)

The role of copper crystallization and segregation toward enhanced methanol synthesis via CO2 hydrogenation over CuZrO2 catalysts: A combined experimental and computational study - Francielle C.F. Marcos; Raphael S. Alvim; Lili Lin; Luis E. Betancourt; Davi D. Petrolini; Sanjaya D. Senanayake; Rita M.B. Alves; José M. Assaf; Jose A. Rodriguez; Reinaldo Giudici; Elisabete M. Assaf (Chemical Engineering Journal, 2023)

Mechanistic insight into the synthesis of fucooligosaccharides by α-L-fucosidase from Thermotoga maritima belonging to the GH29 family: in silico study - Mauricio E. Pavón-Chimal; Carlos Jiménez-Pérez; Francisco Guzmán-Rodriguez; Sergio Alatorre-Santamaría; Luis G. González-Olivares; Mariano García-Garibay; Lorena Gómez-Ruiz; Gabriela Rodríguez-Serrano; Alma E. Cruz-Guerrero (Biologia, 2022)

Determination of the natural potential groundwater recharge in the Valle Alto basin, Bolivia, through a soil water balance - Cristian J. Apaza-Coria; Inti E. Rodriguez-Levy; Mirko Delfín Soruco; Marijke Huysmans (Hydrogeology Journal, 2022)

Elevated Winter Stream Temperatures below Wastewater Treatment Plants Shift Reproductive Development of Female Johnny Darter Etheostoma nigrum: A Field and Histologic Approach - Catherine M. Adams; Dana L. Winkelman; Paula A. Schaffer; Daniel L. Villeneuve; Jenna E. Cavallin; Michael Ellman; Kelvin Santana Rodriguez; Ryan M. Fitzpatrick (Fishes, 2022)
River water temperatures are increasing globally, particularly in urban systems. In winter, wastewater treatment plant (WWTP) effluent inputs are of particular concern because they increase water temperatures from near freezing to ~7–15 °C. Recent laboratory studies suggest that warm overwinter temperatures impact the reproductive timing of some fishes. To evaluate winter water temperature’s influence in the wild, we sampled Johnny Darter Etheostoma nigrum from three urban South Platte River tributaries in Colorado upstream and downstream of WWTP effluent discharge sites. Fish were collected weekly during the spring spawning season of 2021 and reproductive development was determined from histological analysis of the gonads. Winter water temperatures were approximately 5–10 °C greater ~300 m downstream of the WWTP effluent compared to upstream sites, and approximately 3 °C warmer at sampling sites ~5000 m downstream of the effluent discharge. Females collected downstream of WWTP effluent experienced accelerated reproductive development compared to upstream by 1–2 weeks. Water quality, including total estrogenicity, and spring water temperatures did not appear to explain varying reproductive development. It appears that small increases in winter water temperature influence the reproductive timing in E. nigrum. Further investigations into how shifts in reproductive timing influence other population dynamics are warranted.

Research progress on faba bean and faba forage in food and feed types, physiochemical, nutritional, and molecular structural characteristics with molecular spectroscopy - Victor H. Guevara Oquendo; Maria E. Rodriguez Espinosa; Peiqiang Yu (Critical Reviews in Food Science and Nutrition, 2022)

Novel sustainable composites made of car’s waste and sodium titanate for the efficient photocatalytic removal of the bromophenol blue dye: study under solar and UV–Vis light - Ernesto Valadez-Renteria; Jorge Oliva; Nayeli E. Navarro-Garcia; Vicente Rodriguez-Gonzalez (Environmental Science and Pollution Research, 2022)

Correction: Amphibian phylogenetic diversity in the face of future climate change: not so good news for the Chilean biodiversity hotspot - Leonardo J. Rodriguez; Olga A. Barbosa; Claudio Azat; Mario Alvarado-Rybak; Claudio Correa; Marco A. Méndez; Felipe N. Moreno-Gómez; Felipe E. Rabanal; Marcela A. Vidal; Nelson A. Velásquez; Leonardo D. Bacigalupe (Biodiversity and Conservation, 2022)

Amphibian phylogenetic diversity in the face of future climate change: not so good news for the chilean biodiversity hotspot - Leonardo J. Rodriguez; Olga A. Barbosa; Claudio Azat; Mario Alvarado-Rybak; Claudio Correa; Marco A. Méndez; Felipe N. Moreno-Gómez; Felipe E. Rabanal; Marcela A. Vidal; Nelson A. Velásquez; Leonardo D. Bacigalupe (Biodiversity and Conservation, 2022)

The Colombian geochronological database (CGD) - Andres F. Rodriguez-Corcho; Yamirka Rojas-Agramonte; Johana A. Barrera-Gonzalez; Maria P. Marroquin-Gomez; Sarah Bonilla-Correa; David Izquierdo-Camacho; Sofia M. Delgado-Balaguera; David Cartwright-Buitrago; Maria D. Muñoz-Granados; William G. Carantón-Mateus; Alejandro Corrales-García; Andrés F. Laverde-Martinez; et al. (International Geology Review, 2022)

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Anthropogenic Marsh Impoundments Alter Collective Tendency in Schooling Fish - Ivan I. Rodriguez-Pinto; Guillaume Rieucau; Nils Olav Handegard; Matthew E. Kimball; Kevin M. Boswell (Estuaries and Coasts, 2022)

A Comprehensive, FAIR File Format for Neuroanatomical Structure Modeling - A. E. Sullivan; S. J. Tappan; P. J. Angstman; A. Rodriguez; G. C. Thomas; D. M. Hoppes; M. A. Abdul-Karim; M. L. Heal; Jack R. Glaser (Neuroinformatics, 2022)
With advances in microscopy and computer science, the technique of digitally reconstructing, modeling, and quantifying microscopic anatomies has become central to many fields of biological research. MBF Bioscience has chosen to openly document their digital reconstruction file format, the Neuromorphological File Specification, available at www.mbfbioscience.com/filespecification (Angstman et al., 2020). The format, created and maintained by MBF Bioscience, is broadly utilized by the neuroscience community. The data format’s structure and capabilities have evolved since its inception, with modifications made to keep pace with advancements in microscopy and the scientific questions raised by worldwide experts in the field. More recent modifications to the neuromorphological file format ensure it abides by the Findable, Accessible, Interoperable, and Reusable (FAIR) data principles promoted by the International Neuroinformatics Coordinating Facility (INCF; Wilkinson et al., Scientific Data, 3 , 160018,, 2016). The incorporated metadata make it easy to identify and repurpose these data types for downstream applications and investigation. This publication describes key elements of the file format and details their relevant structural advantages in an effort to encourage the reuse of these rich data files for alternative analysis or reproduction of derived conclusions.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Displacement-based seismic design of buildings with thin reinforced concrete structural walls with a single curtain of welded wire mesh - Mario E. Rodriguez (Bulletin of Earthquake Engineering, 2022)

Extreme climate refugia: a case study of wild relatives of cacao (Theobroma cacao) in Colombia - Carlos E. González-Orozco; Mario Porcel; Caren Rodriguez-Medina; Roxana Yockteng (Biodiversity and Conservation, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Practical evaluation of single-frequency dGNSS for monitoring slow-moving landslides - Rodriguez J; Deane E; Hendry M. T; Macciotta R; Evans T; Gräpel C; Skirrow R (Landslides, 2021)

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Host genetic polymorphisms associated with beta human papillomavirus seropositivity - Annika Antonsson; Astrid J. Rodriguez-Acevedo; Upekha E. Liyanage; Maria Celia B. Hughes; Jolieke C. van der Pols; Adele C. Green (Archives of Virology, 2021)

Early 21st Century cyclone climatology: a 3D perspective.Basic Characterization - Susan G. Lakkis; Pablo O. Canziani; Joaquín O. Rodriguez; Adrián E. Yuchechen; Alan O'Neill; Kim H. Albers; Kevin Hodges (International Journal of Climatology, 2021)
Extra‐tropical cyclones are a relevant feature in the climate at middle and high latitudes. Despite their importance, most studies typically focus only on cyclones identified at a single atmospheric level and on events close to the surface. This paper provides a new perspective on the Southern Hemisphere (SH) cyclone events based on the multilevel cyclone tracking algorithm STACKER. The algorithm, using relative vorticity, detects the raw tracks at single levels and objectively combines them to provide the 3D events and their evolutionary timeline. As a result, a 3D cyclone climatology, based on ECMWF Reanalysis ERA‐I data from 12 pressure levels in the troposphere and lowermost stratosphere is presented. To the best of our knowledge, this is the first analysis carried out throughout the troposphere and the lowermost extratropical/subpolar stratosphere in order to give a comprehensive picture of the cyclone events as physical entities throughout their lifetime. Cyclone properties analysed are track densities, translational velocity, vorticity and lifetimes. For the subtropical and extra‐tropical SH, results support many previous ideas about cyclone characteristics, but new insights are also obtained. A total of 58,231 multilevel cyclone events lasting at least 2 days were detected, with vertical structures spanning two or more levels. This means an average of 303 cyclone events of all types per month, between 2001 and 2017, disregarding seasonality. Results show that cyclones are most frequently detected at the lowest levels of 925 and 700 hPa. By considering that cyclonic systems can be grouped into families according to their vertical extent, results per month on average show that shallow systems are the most frequent events with approximately 248 systems detected, followed by 43 intermediary and 11 deep events. Shallow and deep systems have a large percentage of events with genesis at 925 and 700 hPa. Density statistics show that shallow events are present at all latitude ranges mostly poleward of 30°S with high‐ and medium‐intensities, while intermediate ones are mostly restricted to mid‐latitudes and deep events are mostly confined to sub‐polar and polar latitudes. Cyclones over Antarctica seem to be mostly intermediary and deep cyclones, with longer lifetimes and lower velocities.

Managing groundwater supplies subject to drought: perspectives on current status and future priorities from England (UK) - M. J. Ascott; J. P. Bloomfield; I. Karapanos; C. R. Jackson; R. S. Ward; A. B. McBride; B. Dobson; N. Kieboom; I. P. Holman; A. F. Van Loon; E. J. Crane; B. Brauns; et al. (Hydrogeology Journal, 2021)
Effective management of groundwater resources during drought is essential. How is groundwater currently managed during droughts, and in the face of environmental change, what should be the future priorities? Four themes are explored, from the perspective of groundwater management in England (UK): (1) integration of drought definitions; (2) enhanced fundamental monitoring; (3) integrated modelling of groundwater in the water cycle; and (4) better information sharing. Whilst these themes are considered in the context of England, globally, they are relevant wherever groundwater is affected by drought.

Physicochemical Characterisation of Starches from Six Potato Cultivars Native to the Colombian Andean Region - Posidia Pineda-Gomez; Nathalia Mutis González; Brenda Contreras-Jimenez; Mario E. Rodriguez-Garcia (Potato Research, 2021)

Tryptophan depletion predicts lower positive affect in sexual minority men living with HIV who use methamphetamine - Ji-Young Lee; Tiffany R. Glynn; Judith T. Moskowitz; Dietmar Fuchs; Torsten B. Neilands; Samantha E. Dilworth; Daniel J. Feaster; Allan Rodriguez; Adam W. Carrico (Journal of NeuroVirology, 2021)

A 3D construct based on mesenchymal stromal cells, collagen microspheres and plasma clot supports the survival, proliferation and differentiation of hematopoietic cells in vivo - Carlos Bello-Rodriguez; Olga Wittig; Dylana Diaz-Solano; Pura Bolaños; Jose E. Cardier (Cell and Tissue Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Lean on Your Land Grant: One University’s Approach to Address the Food Supply Chain Workforce during the COVID-19 Pandemic - S. Dee Jepsen; Lisa Pfeifer; Lyda G. Garcia; Zoë Plakias; Shoshanah Inwood; Joy N. Rumble; Mary T. Rodriguez; Judit E. Puskas; Samuel G. Custer (Journal of Agromedicine, 2020)

Nutrient Pollution and Predation Differentially Affect Innate Immune Pathways in the Coral Porites porites - Katherine E. Dougan; Mark C. Ladd; Corinne Fuchs; Rebecca Vega Thurber; Deron E. Burkepile; Mauricio Rodriguez-Lanetty (Frontiers in Marine Science, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

The Effect of Short-Term Physical Activity on the Oxidative Stress in Rats with Different Stress Resistance Profiles in Cerebral Hypoperfusion - Vladimir V. Chrishtop; Irina K. Tomilova; Tatiana A. Rumyantseva; Elizaveta V. Mikhaylenko; Marco F. Avila-Rodriguez; Liudmila M. Mikhaleva; Vladimir N. Nikolenko; Siva G. Somasundaram; Cecil E. Kirkland; Sergey O. Bachurin; Gjumrakch Aliev (Molecular Neurobiology, 2020)

Onion waste recycling by vermicomposting: nutrients recovery and agronomical assessment - G. Pellejero; K. Rodriguez; G. Ashchkar; E. Vela; C. García-Delgado; R. Jiménez-Ballesta (International Journal of Environmental Science and Technology, 2020)

Genome repository of oil systems: An interactive and searchable database that expands the catalogued diversity of crude oil‐associated microbes - Smruthi Karthikeyan; Luis M. Rodriguez‐R; Patrick Heritier‐Robbins; Janet K. Hatt; Markus Huettel; Joel E. Kostka; Konstantinos T. Konstantinidis (Environmental Microbiology, 2020)
Summary Microbial communities ultimately control the fate of petroleum hydrocarbons (PHCs) that enter the natural environment, but the interactions of microbes with PHCs and the environment are highly complex and poorly understood. Genome‐resolved metagenomics can help unravel these complex interactions. However, the lack of a comprehensive database that integrates existing genomic/metagenomic data from oil environments with physicochemical parameters known to regulate the fate of PHCs currently limits data analysis and interpretations. Here, we curated a comprehensive, searchable database that documents microbial populations in natural oil ecosystems and oil spills, along with available underlying physicochemical data, geocoded via geographic information system to reveal their geographic distribution patterns. Analysis of the ~2000 metagenome‐assembled genomes (MAGs) available in the database revealed strong ecological niche specialization within habitats. Over 95% of the recovered MAGs represented novel taxa underscoring the limited representation of cultured organisms from oil‐contaminated and oil reservoir ecosystems. The majority of MAGs linked to oil‐contaminated ecosystems were detectable in non‐oiled samples from the Gulf of Mexico but not in comparable samples from elsewhere, indicating that the Gulf is primed for oil biodegradation. The repository should facilitate future work toward a predictive understanding of the microbial taxa and their activities that control the fate of oil spills.

The nervous system component of the mesentery of the sea cucumber Holothuria glaberrima in normal and regenerating animals - Christian Nieves-Ríos; Samuel Alvarez-Falcón; Sonya Malavez; Jannette Rodriguez-Otero; José E. García-Arrarás (Cell and Tissue Research, 2020)

Adenovirus-Mediated Transduction of Insulin-Like Growth Factor 1 Protects Hippocampal Neurons from the Toxicity of Aβ Oligomers and Prevents Memory Loss in an Alzheimer Mouse Model - Maria Clara Selles; Juliana T. S. Fortuna; Maria F. Zappa-Villar; Yasmin P. R. de Faria; Amanda S. Souza; Claudia K. Suemoto; Renata E. P. Leite; Roberta D. Rodriguez; Lea T. Grinberg; Paula C. Reggiani; Sergio T. Ferreira (Molecular Neurobiology, 2020)

Low-density open-cell flexible polyolefin foams as efficient materials for oil absorption: influence of tortuosity on oil absorption - E. Lopez-Gonzalez; C. Saiz-Arroyo; M. A. Rodriguez-Perez (International Journal of Environmental Science and Technology, 2020)

Evaluating the performance of freshwater macroalgae in the bioremediation of nutrient-enriched water in temperate environments - J. M. Valero-Rodriguez; S. E. Swearer; T. Dempster; R. de Nys; A. J. Cole (Journal of Applied Phycology, 2020)

Development of a Co2+/PMS process involving target contaminant degradation and PMS decomposition - O. M. Rodriguez-Narvaez; M. O. A. Pacheco-Alvarez; K. Wróbel; J. Páramo-Vargas; E. R. Bandala; E. Brillas; J. M. Peralta-Hernandez (International Journal of Environmental Science and Technology, 2020)

A comparison of regional brain volumes and white matter connectivity in subjects with stimulant induced psychosis versus schizophrenia - Peter D. Alexander; Kristina M. Gicas; Alex Cheng; Donna J. Lang; Ric M. Procyshyn; Alexandra T. Vertinsky; William J. Panenka; Allen E. Thornton; Alexander Rauscher; Jamie Y. X. Wong; Tasha Chan; Andrea A. Jones; et al. (Psychopharmacology, 2019)

Free‐living and symbiotic lifestyles of a thermotolerant coral endosymbiont display profoundly distinct transcriptomes under both stable and heat stress conditions - Anthony J. Bellantuono; Katherine E. Dougan; Camila Granados‐Cifuentes; Mauricio Rodriguez‐Lanetty (Molecular Ecology, 2019)
Reef‐building corals depend upon a nutritional endosymbiosis with photosynthetic dinoflagellates of the family Symbiodiniaceae for the majority of their energetic needs. While this mutualistic relationship is impacted by numerous stressors, warming oceans are a predominant threat to coral reefs, placing the future of the world's reefs in peril. Some Symbiodiniaceae species exhibit tolerance to thermal stress, but the in hospite symbiont response to thermal stress is underexplored. To describe the underpinnings of symbiosis and heat stress response, we compared in hospite and free‐living transcriptomes of Durusdinium trenchii , a pan‐tropical heat‐tolerant Symbiodiniaceae species, under stable temperature conditions and acute hyperthermal stress. We discovered that symbiotic state was a larger driver of the transcriptional landscape than heat stress. The majority of differentially expressed transcripts between in hospite and free‐living cells were downregulated, suggesting the in hospite condition is associated with the shutdown of numerous processes uniquely required for a free‐living lifestyle. In the free‐living state, we identified enrichment for numerous cell signalling pathways and other functions related to detecting and responding to a changing environment, as well as transcripts relating to mitosis, meiosis, and motility. In contrast, in hospite cells exhibited enhanced transcriptional activity for photosynthesis and carbohydrate transport as well as chromatin modifications and a disrupted circadian clock. Hyperthermal stress induced drastic alteration of transcriptional activity in hospite, suggesting symbiotic engagement with the host elicited an exacerbated stress response when compared to free‐living D. trenchii . Altogether, the dramatic differences in gene expression between in hospite and free‐living D. trenchii indicate the importance of considering symbiotic state in investigations of symbiosis and hyperthermal stress in Symbiodiniaceae.

Protected area downgrading, downsizing, and degazettement as a threat to iconic protected areas - Siyu Qin; Rachel E. Golden Kroner; Carly Cook; Anteneh T. Tesfaw; Rowan Braybrook; Carlos Manuel Rodriguez; Claire Poelking; Michael B. Mascia (Conservation Biology, 2019)
Protected areas (PAs) are expected to conserve nature and provide ecosystem services in perpetuity, yet widespread protected area downgrading, downsizing, and degazettement (PADDD) may compromise these objectives. Even iconic protected areas are vulnerable to PADDD, although these PADDD events are often unrecognized. We identified 23 enacted and proposed PADDD events within World Natural Heritage Sites and examined the history, context, and consequences of PADDD events in 4 iconic PAs (Yosemite National Park, Arabian Oryx Sanctuary, Yasuní National Park, and Virunga National Park). Based on insights from published research and international workshops, these 4 cases revealed the diverse pressures brought on by competing interests to develop or exploit natural landscapes and the variety of mechanisms that enables PADDD. Knowledge gaps exist in understanding of the conditions through which development pressures translate to PADDD events and their impacts, partially due to a lack of comprehensive PADDD records. Future research priorities should include comprehensive regional and country‐level profiles and analysis of risks, impacts, and contextual factors related to PADDD. Policy options to better govern PADDD include improving tracking and reporting of PADDD events, establishing transparent PADDD policy processes, coordinating among legal frameworks, and mitigating negative impacts of PADDD. To support PADDD research and policy reforms, enhanced human and financial capacities are needed to train local researchers and to host publicly accessible data. As the conservation community considers the achievements of Aichi Target 11 and moves toward new biodiversity targets beyond 2020, researchers, practitioners, and policy makers need to work together to better track, assess, and govern PADDD globally.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

The Neuronal Ischemic Tolerance Is Conditioned by the Tp53 Arg72Pro Polymorphism - Maria E. Ramos-Araque; Cristina Rodriguez; Rebeca Vecino; Elisa Cortijo Garcia; Mercedes de Lera Alfonso; Mercedes Sanchez Barba; Laura Colàs-Campàs; Francisco Purroy; Juan F. Arenillas; Angeles Almeida; Maria Delgado-Esteban (Translational Stroke Research, 2019)
Cerebral preconditioning (PC) confers endogenous brain protection after stroke. Ischemic stroke patients with a prior transient ischemic attack (TIA) may potentially be in a preconditioned state. Although PC has been associated with the activation of pro-survival signals, the mechanism by which preconditioning confers neuroprotection is not yet fully clarified. Recently, we have described that PC-mediated neuroprotection against ischemic insult is promoted by p53 destabilization, which is mediated by its main regulator MDM2. Moreover, we have previously described that the human Tp53 Arg72Pro single nucleotide polymorphism (SNP) controls susceptibility to ischemia-induced neuronal apoptosis and governs the functional outcome of patients after stroke. Here, we studied the contribution of the human Tp53 Arg72Pro SNP on PC-induced neuroprotection after ischemia. Our results showed that cortical neurons expressing the Pro72-p53 variant exhibited higher PC-mediated neuroprotection as compared with Arg72-p53 neurons. PC prevented ischemia-induced nuclear and cytosolic p53 stabilization in Pro72-p53 neurons. However, PC failed to prevent mitochondrial p53 stabilization, which occurs in Arg72-p53 neurons after ischemia. Furthermore, PC promoted neuroprotection against ischemia by controlling the p53/active caspase-3 pathway in Pro72-p53, but not in Arg72-p53 neurons. Finally, we found that good prognosis associated to TIA within 1 month prior to ischemic stroke was restricted to patients harboring the Pro72 allele. Our findings demonstrate that the Tp53 Arg72Pro SNP controls PC-promoted neuroprotection against a subsequent ischemic insult by modulating mitochondrial p53 stabilization and then modulates TIA-induced ischemic tolerance.

pH Variability Exacerbates Effects of Ocean Acidification on a Caribbean Crustose Coralline Alga - Maggie D. Johnson; Lucia M. Rodriguez Bravo; Shevonne E. O’Connor; Nicholas F. Varley; Andrew H. Altieri (Frontiers in Marine Science, 2019)

Cellular Uptake of MCT1 Inhibitors AR-C155858 and AZD3965 and Their Effects on MCT-Mediated Transport of L-Lactate in Murine 4T1 Breast Tumor Cancer Cells - Xiaowen Guan; Vivian Rodriguez-Cruz; Marilyn E. Morris (The AAPS Journal, 2019)

Potential value of tedera (B. bituminosa) as high protein resource for poultry feed - M. Barbera; M.C. Muñoz; E. Rodriguez-Ponce; M.R. Ventura (Tropical Animal Health and Production, 2019)

Serum P-glycoprotein level: a potential biomarker of DMARD failure in patients with rheumatoid arthritis - E. E. Perez-Guerrero; L. Gonzalez-Lopez; J. F. Muñoz-Valle; J. C. Vasquez-Jimenez; M. Ramirez-Villafaña; E. N. Sanchez-Rodriguez; S. R. Gutierrez-Ureña; S. Cerpa-Cruz; E. A. Aguilar-Chavez; E. G. Cardona-Muñoz; M. L. Vazquez-Villegas; A. M. Saldaña-Cruz; et al. (Inflammopharmacology, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Comparing the impact of a grazing regime with European bison versus one with free-ranging cattle on coastal dune vegetation in the Netherlands - E. Valdés-Correcher; Esther Rodriguez; Yvonne J. M. Kemp; Martin J. Wassen; Joris P. G. M. Cromsigt (Mammal Research, 2018)

Tibolone Reduces Oxidative Damage and Inflammation in Microglia Stimulated with Palmitic Acid through Mechanisms Involving Estrogen Receptor Beta - Oscar Hidalgo-Lanussa; Marco Ávila-Rodriguez; Eliana Baez-Jurado; Jairo Zamudio; Valentina Echeverria; Luis Miguel Garcia-Segura; George E. Barreto (Molecular Neurobiology, 2018)

Invasive pulmonary aspergillosis is associated with adverse clinical outcomes in critically ill patients receiving veno-venous extracorporeal membrane oxygenation - I. Rodriguez-Goncer; S. Thomas; P. Foden; M. D. Richardson; A. Ashworth; J. Barker; C. G. Geraghty; E. G. Muldoon; T. W. Felton (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Metal contaminations impact archaeal community composition, abundance and function in remote alpine lakes - Sergi Compte‐Port; Carles M. Borrego; Hélène Moussard; Mathilde Jeanbille; Claudia Ximena Restrepo‐Ortiz; Alberto de Diego; Azibar Rodriguez‐Iruretagoiena; Ainara Gredilla; Silvia Fdez‐Ortiz de Vallejuelo; Pierre E. Galand; Dimitri Kalenitchenko; Jean‐Luc Rols; et al. (Environmental Microbiology, 2018)
Summary Using the 16S rRNA and mcrA genes, we investigated the composition, abundance and activity of sediment archaeal communities within 18 high‐mountain lakes under contrasted metal levels from different origins (bedrock erosion, past‐mining activities and atmospheric depositions). Bathyarchaeota, Euryarchaeota and Woesearchaeota were the major phyla found at the meta‐community scale, representing 48%, 18.3% and 15.2% of the archaeal community respectively. Metals were equally important as physicochemical variables in explaining the assemblage of archaeal communities and their abundance. Methanogenesis appeared as a process of central importance in the carbon cycle within sediments of alpine lakes as indicated by the absolute abundance of methanogen 16S rRNA and mcrA gene transcripts (10 5 to 10 9 copies g −1 ). We showed that methanogen abundance and activity were significantly reduced with increasing concentrations of Pb and Cd, two indicators of airborne metal contaminations. Considering the ecological importance of methanogenesis in sediment habitats, these metal contaminations may have system wide implications even in remote area such as alpine lakes. Overall, this work was pioneer in integrating the effect of long‐range atmospheric depositions on archaeal communities and indicated that metal contamination might significantly compromise the contribution of Archaea to the carbon cycling of the mountain lake sediments.

Characterisation of ground motion recording stations in the Groningen gas field - Rik Noorlandt; Pauline P. Kruiver; Marco P. E. de Kleine; Marios Karaoulis; Ger de Lange; Antonio Di Matteo; Julius von Ketelhodt; Elmer Ruigrok; Benjamin Edwards; Adrian Rodriguez-Marek; Julian J. Bommer; Jan van Elk; et al. (Journal of Seismology, 2018)

Influence of increasing temperature on the scorpion sting incidence by climatic regions - Magali Hurtado‐Díaz; José Guzmán‐Ontiveros; Luis A. Arias‐Medellín; Leticia Hernández‐Cadena; Grea L. Moreno‐Banda; Sandra L. Rodriguez‐Dozal; José L. Texcalac‐Sangrador; Pamela E. Zúñiga‐Bello; Horacio Riojas‐Rodríguez (International Journal of Climatology, 2018)
Scorpion stings are a major public health concern representing a frequent cause of intoxication in many countries. The present study aims to examine the impact of climate variability in different climatic regions of the state of Morelos in Mexico on the incidence of scorpion stings. An ecological study was conducted using a retrospective time‐series analysis. Weekly reported scorpion sting cases from the Unique System of Information for Epidemiological Surveillance (SUIVE) and daily temperature and precipitation from the National Meteorological Service were obtained from 1999 to 2007. The geographical region of study was divided according three climatic conditions into Hot region (HR), Warm region (WR) and Cold region (CR). Generalized Linear Models were used to estimate the percent change [95% confidence intervals (CI)] of scorpion sting cases associated to an increase of 1 °C of temperature and 1 cm of precipitation in each climatic region. During the period of study there were 281 076 scorpion sting cases reported in the State of Morelos, Mexico. Positive correlations among temperature and scorpion sting cases were found ( R = 0.59 and 0.70 in the HR and WR, respectively). Regions with the hottest temperatures had the greatest effect, showing a 9.8% (CI 95%: 8.30–11.30) increase in scorpion sting cases per 1 °C increased in temperature. Increase in minimum and maximum temperatures have a delayed effect on scorpion stings cases and these may vary by climatic region.

Brain-specific HIV Nef identified in multiple patients with neurological disease - Susanna L. Lamers; Gary B. Fogel; Enoch S. Liu; Andrew E. Barbier; Christopher W. Rodriguez; Elyse J. Singer; David J. Nolan; Rebecca Rose; Michael S. McGrath (Journal of NeuroVirology, 2018)

Higher In vitro Proliferation Rate of Rhizopus oryzae in Blood of Diabetic Individuals in Chronic Glycaemic Control Compared with Non-diabetic Individuals - Grace Salazar-Tamayo; Luis E. López-Jácome; Jesús Resendiz-Sanchez; Rafael Franco-Cendejas; Patricia Rodriguez-Zulueta; Dora E. Corzo-León (Mycopathologia, 2017)

Impact of rapid diagnosis of Staphylococcus aureus bacteremia from positive blood cultures on patient management - M. P. Romero-Gómez; E. Cendejas-Bueno; J. García Rodriguez; J. Mingorance (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Ocular flutter following Zika virus infection - Emely Karam; Jose Giraldo; Flor Rodriguez; Carlos E. Hernandez-Pereira; Alfonso J. Rodriguez-Morales; Gabriela M. Blohm; Alberto E. Paniz-Mondolfi (Journal of NeuroVirology, 2017)

Growth and mortality of larval anchoveta Engraulis ringens , in northern Chile during winter and their relationship with coastal hydrographic conditions - Jorge E. Contreras; Camilo Rodriguez‐Valentino; Mauricio F. Landaeta; Guido Plaza; Manuel I. Castillo; Mónica Alvarado‐Niño (Fisheries Oceanography, 2017)
Larval growth, age, growth effect and instantaneous mortality were estimated in anchoveta, Engraulis ringens , collected biweekly during the austral winter of 2014 in nearshore waters off Bay of Antofagasta (23°41′W–70°30′S), northern Chile. Through measuring standard length ( SL ) and sagitta microstructure analysis, it was estimated that the growth rate of E. ringens larvae decreased from June (0.85 mm day −1 ) to August (0.50 mm day −1 ). However, the water temperature was homogeneous during the sampling dates (14.6, 15.2, 14.4, and 14.6°C), suggesting that the decelerating larval growth was not linked to changes in sea temperature. Additionally, larvae with slow growth have larger otoliths compared with conspecifics with fast growth (growth effect). Larval mortality rates tended to decrease until the middle of July (0.18 per day) but increased to 0.25 per day in early August, which coincided with lower food availability (i.e., chlorophyll‐a, 2.7–5.6 mg m −3 ) and a high occurrence of smaller larvae (1.58–11.5 mm). Partial least squares analysis indicates low covariance between the biological and oceanographic variables ( PLS : 11.71%), suggesting that other factors, such as parental effects, may explain the abrupt decrease in the larval growth rates.

Stochastic evaluation of the impact of sewer inlets’ hydraulic capacity on urban pluvial flooding - João P. Leitão; Nuno E. Simões; Rui Daniel Pina; Susana Ochoa-Rodriguez; Christian Onof; Alfeu Sá Marques (Stochastic Environmental Research and Risk Assessment, 2017)

Aerobic interval training reduces vascular resistances during submaximal exercise in obese metabolic syndrome individuals - Ricardo Mora-Rodriguez; V. E. Fernandez-Elias; F. Morales-Palomo; J. G. Pallares; M. Ramirez-Jimenez; J. F. Ortega (European Journal of Applied Physiology, 2017)

CO 2 exchange and evapotranspiration across dryland ecosystems of southwestern North America - Joel A. Biederman; Russell L. Scott; Tom W. Bell; David R. Bowling; Sabina Dore; Jaime Garatuza‐Payan; Thomas E. Kolb; Praveena Krishnan; Dan J. Krofcheck; Marcy E. Litvak; Gregory E. Maurer; Tilden P. Meyers; et al. (Global Change Biology, 2017)
Global‐scale studies suggest that dryland ecosystems dominate an increasing trend in the magnitude and interannual variability of the land CO 2 sink. However, such analyses are poorly constrained by measured CO 2 exchange in drylands. Here we address this observation gap with eddy covariance data from 25 sites in the water‐limited Southwest region of North America with observed ranges in annual precipitation of 100–1000 mm, annual temperatures of 2–25°C, and records of 3–10 years (150 site‐years in total). Annual fluxes were integrated using site‐specific ecohydrologic years to group precipitation with resulting ecosystem exchanges. We found a wide range of carbon sink/source function, with mean annual net ecosystem production ( NEP ) varying from ‐350 to +330 gC m −2 across sites with diverse vegetation types, contrasting with the more constant sink typically measured in mesic ecosystems. In this region, only forest‐dominated sites were consistent carbon sinks. Interannual variability of NEP , gross ecosystem production ( GEP ), and ecosystem respiration (R eco ) was larger than for mesic regions, and half the sites switched between functioning as C sinks/C sources in wet/dry years. The sites demonstrated coherent responses of GEP and NEP to anomalies in annual evapotranspiration ( ET ), used here as a proxy for annually available water after hydrologic losses. Notably, GEP and R eco were negatively related to temperature, both interannually within site and spatially across sites, in contrast to positive temperature effects commonly reported for mesic ecosystems. Models based on MODIS satellite observations matched the cross‐site spatial pattern in mean annual GEP but consistently underestimated mean annual ET by ~50%. Importantly, the MODIS ‐based models captured only 20–30% of interannual variation magnitude. These results suggest the contribution of this dryland region to variability of regional to global CO 2 exchange may be up to 3–5 times larger than current estimates.

SLC and ABC Transporters: Expression, Localization, and Species Differences at the Blood-Brain and the Blood-Cerebrospinal Fluid Barriers - Marilyn E. Morris; Vivian Rodriguez-Cruz; Melanie A. Felmlee (The AAPS Journal, 2017)

L-Type Calcium Channels Modulation by Estradiol - Nelson E. Vega-Vela; Daniel Osorio; Marco Avila-Rodriguez; Janneth Gonzalez; Luis Miguel García-Segura; Valentina Echeverria; George E. Barreto (Molecular Neurobiology, 2017)

Influence of dissolved organic matter and oil on the biosorption of BTEX by macroalgae in single and multi-solute systems - Mayra Cecilia Rodriguez-Hernandez; Carlos E. Flores-Chaparro; Jose Rene Rangel-Mendez (Environmental Science and Pollution Research, 2017)

Satellite Remote Sensing for Coastal Management: A Review of Successful Applications - Matthew J. McCarthy; Kaitlyn E. Colna; Mahmoud M. El-Mezayen; Abdiel E. Laureano-Rosario; Pablo Méndez-Lázaro; Daniel B. Otis; Gerardo Toro-Farmer; Maria Vega-Rodriguez; Frank E. Muller-Karger (Environmental Management, 2017)

Environment and life cycles influence distribution patterns of hydromedusae in austral South America - Carolina S. Rodriguez; Antonio C. Marques; Hermes W. Mianzan; Valquiria B. Tronolone; Alvaro E. Migotto; Gabriel N. Genzano (Marine Biology Research, 2017)

Evaluation of antimicrobial persistent activity of alcohol-based hand antiseptics against bacterial contamination - R. M. López-Gigosos; E. Mariscal-López; M. Gutierrez-Bedmar; A. García-Rodriguez; A. Mariscal (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Hibernation-based blood loss therapy increases survivability of lethal hemorrhagic shock in rats - Cecilia E. Perez de Lara Rodriguez; Lester R. Drewes; Matthew T. Andrews (Journal of Comparative Physiology B, 2017)

Identification of MSH2 inversion of exons 1–7 in clinical evaluation of families with suspected Lynch syndrome - Maureen E. Mork; Andrea Rodriguez; Melissa W. Taggart; Miguel A. Rodriguez-Bigas; Patrick M. Lynch; Sarah A. Bannon; Y. Nancy You; Eduardo Vilar (Familial Cancer, 2017)

Methylene blue modulates functional connectivity in the human brain - Pavel Rodriguez; Amar P. Singh; Kristen E. Malloy; Wei Zhou; Douglas W. Barrett; Crystal G. Franklin; Wilson B. Altmeyer; Juan E. Gutierrez; Jinqi Li; Betty L. Heyl; Jack L. Lancaster; F. Gonzalez-Lima; et al. (Brain Imaging and Behavior, 2017)

Acer binzayedii (Sapindaceae), a new maple species from Mexico - Yalma L. Vargas-Rodriguez; Lowell E. Urbatsch; Vesna Karaman-Castro; Blanca L. Figueroa-Rangel (Brittonia, 2017)

A comparison of psychotic symptoms in subjects with methamphetamine versus cocaine dependence - Peter D Alexander; Kristina M Gicas; Taylor S Willi; Clara N Kim; Veronika Boyeva; Ric M Procyshyn; Geoff N. Smith; Allen E Thornton; William J Panenka; Andrea A. Jones; Fidel Vila-Rodriguez; Donna J. Lang; et al. (Psychopharmacology, 2017)

Occurrence of Photobacterium damselae Subsp. Piscicida in Sea-Cage Farmed Meagre (Argyrosomus regius) in Tenerife, Canary Islands, Spain - J. Z. Costa; Ú. McCarthy; O. Perez; E. Ramos; M. Rodriguez; O. Monterroso; R. Riera (Thalassas: An International Journal of Marine Sciences, 2017)

Epidemiology and reporting of candidaemia in Belgium: a multi-centre study - C. Trouvé; S. Blot; M.-P. Hayette; S. Jonckheere; S. Patteet; H. Rodriguez-Villalobos; F. Symoens; E. Van Wijngaerden; K. Lagrou (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Expression and biochemical characteristics of two different aldosterone receptors in both healthy and dilated cardiomyopathy dog heart tissue - Alejandro R. Reynoso Palomar; Moncerrat Rodriguez Bravo; Abel E. Villa Mancera; Carlos J. Mucha (Veterinary Research Communications, 2017)

The effect of future climate change on the conservation of Chloraea disoides Lindl. (Orchidaceae) in Chile - C. Atala; L. Muñoz-Tapia; G. Pereira; C. Romero; R. Vargas; I. S. Acuña-Rodriguez; M. A. Molina-Montenegro; E. Brito (Brazilian Journal of Botany, 2017)

Erratum to: Soft Tissue Phantoms for Realistic Needle Insertion: A Comparative Study - Alexander Leibinger; Antonio E. Forte; Zhengchu Tan; Matthew J. Oldfield; Frank Beyrau; Daniele Dini; Ferdinando Rodriguez y Baena (Annals of Biomedical Engineering, 2016)

IFITM3 and severe influenza virus infection. No evidence of genetic association - M. López-Rodríguez; E. Herrera-Ramos; J. Solé-Violán; J. J. Ruíz-Hernández; L. Borderías; J. P. Horcajada; E. Lerma-Chippirraz; O. Rajas; M. Briones; M. C. Pérez-González; M. A. García-Bello; E. López-Granados; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Blade life span, structural investment, and nutrient allocation in giant kelp - Gabriel E. Rodriguez; Daniel C. Reed; Sally J. Holbrook (Oecologia, 2016)

Antibody-Mediated Oligodendrocyte Remyelination Promotes Axon Health in Progressive Demyelinating Disease - Bharath Wootla; Aleksandar Denic; Jens O. Watzlawik; Arthur E. Warrington; Moses Rodriguez (Molecular Neurobiology, 2016)

Identification of a novel PMS2 alteration c.505C>G (R169G) in trans with a PMS2 pathogenic mutation in a patient with constitutional mismatch repair deficiency - Maureen E. Mork; Ester Borras; Melissa W. Taggart; Amanda Cuddy; Sarah A. Bannon; Y. Nancy You; Patrick M. Lynch; Pedro T. Ramirez; Miguel A. Rodriguez-Bigas; Eduardo Vilar (Familial Cancer, 2016)

Free-living culturable bacteria and protozoa from the rhizoplanes of three floating aquatic plant species - E. Quisehuatl-Tepexicuapan; R. Ferrera-Cerrato; H. V. Silva-Rojas; S. Rodriguez-Zaragoza; A. Alarcón; J. J. Almaraz-Suárez (Plant Biosystems, 2016)

Soil mercury levels in the area surrounding the Cerro Prieto geothermal complex, MEXICO - M. A. Pastrana-Corral; F. T. Wakida; E. García-Flores; D. D. Rodriguez-Mendivil; A. Quiñonez-Plaza; T. D. J. Piñon-Colin (Environmental Monitoring and Assessment, 2016)

Recurrence of progressive multifocal leukoencephalopathy despite immune recovery in two HIV seropositive individuals - Kate M. Crossley; Shruti Agnihotri; Joga Chaganti; Michael L. Rodriguez; Leon Patrick McNally; Nagagopal Venna; Sarah E. Turbett; Matthew Gutman; Adrienne Morey; Igor J. Koralnik; Bruce J. Brew (Journal of NeuroVirology, 2016)

Soft Tissue Phantoms for Realistic Needle Insertion: A Comparative Study - Alexander Leibinger; Antonio E. Forte; Zhengchu Tan; Matthew J. Oldfield; Frank Beyrau; Daniele Dini; Ferdinando Rodriguez y Baena (Annals of Biomedical Engineering, 2016)

Amphibian‐killing chytrid in B razil comprises both locally endemic and globally expanding populations - T. S. Jenkinson; C. M. Betancourt Román; C. Lambertini; A. Valencia‐Aguilar; D. Rodriguez; C. H. L. Nunes‐de‐Almeida; J. Ruggeri; A. M. Belasen; D. da Silva Leite; K. R. Zamudio; J. E. Longcore; L. F. Toledo; et al. (Molecular Ecology, 2016)
Chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis ( Bd ), is the emerging infectious disease implicated in recent population declines and extinctions of amphibian species worldwide. Bd strains from regions of disease‐associated amphibian decline to date have all belonged to a single, hypervirulent clonal genotype ( Bd ‐ GPL ). However, earlier studies in the Atlantic Forest of southeastern Brazil detected a novel, putatively enzootic lineage ( Bd ‐Brazil), and indicated hybridization between Bd ‐ GPL and Bd ‐Brazil. Here, we characterize the spatial distribution and population history of these sympatric lineages in the Brazilian Atlantic Forest. To investigate the genetic structure of Bd in this region, we collected and genotyped Bd strains along a 2400‐km transect of the Atlantic Forest. Bd ‐Brazil genotypes were restricted to a narrow geographic range in the southern Atlantic Forest, while Bd ‐ GPL strains were widespread and largely geographically unstructured. Bd population genetics in this region support the hypothesis that the recently discovered Brazilian lineage is enzootic in the Atlantic Forest of Brazil and that Bd ‐ GPL is a more recently expanded invasive. We collected additional hybrid isolates that demonstrate the recurrence of hybridization between panzootic and enzootic lineages, thereby confirming the existence of a hybrid zone in the Serra da Graciosa mountain range of Paraná State. Our field observations suggest that Bd ‐ GPL may be more infective towards native Brazilian amphibians, and potentially more effective at dispersing across a fragmented landscape. We also provide further evidence of pathogen translocations mediated by the Brazilian ranaculture industry with implications for regulations and policies on global amphibian trade.

Loss and gains in ant–plant interactions mediated by extrafloral nectar: fidelity, cheats, and lies - K. Del-Claro; V. Rico-Gray; H. M. Torezan-Silingardi; E. Alves-Silva; R. Fagundes; D. Lange; W. Dáttilo; A. A. Vilela; A. Aguirre; D. Rodriguez-Morales (Insectes Sociaux, 2016)

Assessing the State of Contamination in a Historic Mining Town Using Sediment Chemistry - Mélida Gutiérrez; Shuo-Sheng Wu; Jameelah R. Rodriguez; Ashton D. Jones; Benjamin E. Lockwood (Archives of Environmental Contamination and Toxicology, 2016)

Novel Approaches in Astrocyte Protection: from Experimental Methods to Computational Approaches - Daniel Garzón; Ricardo Cabezas; Nelson Vega; Marcos Ávila-Rodriguez; Janneth Gonzalez; Rosa Margarita Gómez; Valentina Echeverria; Gjumrakch Aliev; George E. Barreto (Journal of Molecular Neuroscience, 2016)

Genetic background of novel sequence types of CTX-M-8- and CTX-M-15-producing Escherichia coli and Klebsiella pneumoniae from public wastewater treatment plants in São Paulo, Brazil - Milena Dropa; Nilton Lincopan; Livia C. Balsalobre; Danielle E. Oliveira; Rodrigo A. Moura; Miriam Rodriguez Fernandes; Quézia Moura da Silva; Glavur R. Matté; Maria I. Z. Sato; Maria H. Matté (Environmental Science and Pollution Research, 2016)

Cryopreserved amniotic membrane as transplant allograft: viability and post-transplant outcome - Natasha M. J. Perepelkin; Kirsten Hayward; Tumelo Mokoena; Michael J. Bentley; Lisa U. Ross-Rodriguez; Leah Marquez-Curtis; Locksley E. McGann; Jelena L. Holovati; Janet A. W. Elliott (Cell and Tissue Banking, 2016)

Adaptation of a Methanogenic Consortium to Arsenite Inhibition - Lucia Rodriguez-Freire; Sarah E. Moore; Reyes Sierra-Alvarez; James A. Field (Water, Air, & Soil Pollution, 2015)

Metal enrichment of soils following the April 2012–2013 eruptive activity of the Popocatépetl volcano, Puebla, Mexico - P. F. Rodriguez-Espinosa; M. P. Jonathan; S. S. Morales-García; Lorena Elizabeth Campos Villegas; E. Martínez-Tavera; N. P. Muñoz-Sevilla; Miguel Alvarado Cardona (Environmental Monitoring and Assessment, 2015)

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Nutrient enrichment intensifies hurricane impact in scrub mangrove ecosystems in the Indian River Lagoon, Florida, USA - Ilka C. Feller; Emily M. Dangremond; Donna J. Devlin; Catherine E. Lovelock; C. Edward Proffitt; Wilfrid Rodriguez (Ecology, 2015)
Mangroves are an ecological assemblage of trees and shrubs adapted to grow in intertidal environments along tropical, subtropical, and warm temperate coasts. Despite repeated demonstrations of their ecologic and economic value, multiple stressors including nutrient over‐enrichment threaten these and other coastal wetlands globally. These ecosystems will be further stressed if tropical storm intensity and frequency increase in response to global climate changes. These stressors will likely interact, but the outcome of that interaction is uncertain. Here, we examined potential interaction between nutrient over‐enrichment and the September 2004 hurricanes. Hurricanes Frances and Jeanne made landfall along Florida's Indian River Lagoon and caused extensive damage to a long‐term fertilization experiment in a mangrove forest, which previously revealed that productivity was nitrogen (N) limited across the forest and, in particular, that N enrichment dramatically increased growth rates and aboveground biomass of stunted Avicennia germinans trees in the interior scrub zone. During the hurricanes, these trees experienced significant defoliation with three to four times greater reduction in leaf area index (LAI) than control trees. Over the long term, the +N scrub trees took four years to recover compared to two years for controls. In the adjacent fringe and transition zones, LAI was reduced by >70%, but with no differences based on zone or fertilization treatment. Despite continued delayed mortality for at least five years after the storms, LAI in the fringe and transition returned to pre‐hurricane conditions in two years. Thus, nutrient over‐enrichment of the coastal zone will increase the productivity of scrub mangroves, which dominate much of the mangrove landscape in Florida and the Caribbean; however, that benefit is offset by a decrease in their resistance and resilience to hurricane damage that has the potential to destabilize the system.

Common polygenic variation contributes to risk of migraine in the Norfolk Island population - A. J. Rodriguez-Acevedo; M. A. Ferreira; Miles C. Benton; Melanie A. Carless; Harald H. Goring; Joanne E. Curran; John Blangero; R. A. Lea; L. R. Griffiths (Human Genetics, 2015)

Cellular metabolism of unnatural sialic acid precursors - Nam D. Pham; Charles S. Fermaintt; Andrea C. Rodriguez; Janet E. McCombs; Nicole Nischan; Jennifer J. Kohler (Glycoconjugate Journal, 2015)

Relationship between muscle water and glycogen recovery after prolonged exercise in the heat in humans - Valentín E. Fernández-Elías; Juan F. Ortega; Rachael K. Nelson; Ricardo Mora-Rodriguez (European Journal of Applied Physiology, 2015)

Oxidized and reduced [2Fe–2S] clusters from an iron(I) synthon - Megan E. Reesbeck; Meghan M. Rodriguez; William W. Brennessel; Brandon Q. Mercado; David Vinyard; Patrick L. Holland (JBIC Journal of Biological Inorganic Chemistry, 2015)

CXCL10/XCL1 fusokine elicits in vitro and in vivo chemotaxis - Yessica E. Sanchez-Lugo; Jose J. Perez-Trujillo; Yolanda Gutierrez-Puente; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha; Oralia Barboza-Quintana; Gerardo E. Muñoz-Maldonado; Odila Saucedo-Cardenas; Roberto Montes de Oca-Luna; Maria J. Loera-Arias (Biotechnology Letters, 2015)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Detection of hotspots and rapid determination of methane emissions from landfills via a ground-surface method - R. Gonzalez-Valencia; F. Magana-Rodriguez; E. Maldonado; J. Salinas; F. Thalasso (Environmental Monitoring and Assessment, 2015)

Geomechanical modelling to assess fault integrity at the CO2CRC Otway Project, Australia - C. M. Aruffo; A. Rodriguez-herrera; E. Tenthorey; F. Krzikalla; J. Minton; A. Henk (Australian Journal of Earth Sciences, 2014)

Fear extinction and acute stress reactivity reveal a role of LPA1 receptor in regulating emotional-like behaviors - C. Pedraza; J. Sánchez-López; E. Castilla-Ortega; C. Rosell-Valle; E. Zambrana-Infantes; M. García-Fernández; F. Rodriguez de Fonseca; J. Chun; L. J. Santín; G. Estivill-Torrús (Brain Structure and Function, 2014)

New subgroup 16SrIII-Y phytoplasmas associated with false-blossom diseased cranberry (Vaccinium macrocarpon) plants and with known and potential insect vectors in New Jersey - I.-M. Lee; J. Polashock; K. D. Bottner-Parker; P. G. Bagadia; C. Rodriguez-Saona; Y. Zhao; R. E. Davis (European Journal of Plant Pathology, 2014)

Considerations for a Pediatric Biopharmaceutics Classification System (BCS): Application to Five Drugs - Shivani V. Gandhi; William Rodriguez; Mansoor Khan; James E. Polli (AAPS PharmSciTech, 2014)

Trophic ecology of Lampanyctus crocodilus on north‐west Mediterranean Sea slopes in relation to reproductive cycle and environmental variables - E. Fanelli; V. Papiol; J. E. Cartes; O. Rodriguez‐Romeu (Journal of Fish Biology, 2014)
This study examined the population structure, reproductive cycle and feeding pattern of the lanternfish Lampanyctus crocodilus in the Balearic Basin (north‐west Mediterranean Sea) from a depth of 450 to 1800 m and at a seasonal scale. Juveniles were mainly located at shallower depths, but also at deepest stations in autumn, while adults mostly inhabited intermediate depths with their centre of population density (CPD) located at 800–1000 m of depth. The migration of adults to deeper depths was detected in late summer to autumn, probably linked to the occurrence of nepheloid layers at c. 1200 m, which in turn enhances the biomass of the zooplankton prey. The diet was mainly based on euphausiids and mysids, with marked seasonal variations both on the upper (450–800 m) and lower (1000–1800 m), where suprabenthic gammariids and pelagic decapods were also dominant. Stomach fullness increased from winter to autumn on the US , while it had a maximum in spring on the LS , in parallel with high consumption of gelatinous zooplankton, which is probably more available after the phytoplankton bloom in late winter. Reproduction occurred in winter, confirmed by the higher percentage of mature females and high gonadosomatic indices ( I G ) at both depth ranges. Hepatosomatic indices ( I H ) showed an inverse trend to I G on the US, except in autumn, and was almost parallel on the LS, probably attributable to the migration of adults, which determined different temporal schemes in energy use and storage for reproduction on the US v . LS. Consistent with the different patterns observed at the two depth ranges, environmental drivers of fullness ( i.e. feeding intensity) and I G (as a proxy of reproductive cycle) differed on the US and LS. The biomass of mysids and euphausiids was the greatest explanatory variables of fullness on the US and LS, pointing to the increasing feeding intensity when a resource was more available. I H also explained fullness, suggesting that greater feeding intensity in pre‐reproductive periods enabled energy storage in the liver. I G was linked directly ( i.e. mysids) or indirectly ( i.e. surface primary production recorded 2 months before sampling) to food availability, implying a rapid response to vertical food inputs by deep‐sea predators. Also, I G in L. crocodilus was related to population density, which suggests aggregations for reproduction. Estimates of L. crocodilus trophic levels, and of other accompanying mesopelagic fishes, indicated that the species feed through a continuum spanning the third trophic level, confirming the key role of mesopelagic fishes in transferring organic carbon between trophic levels. Trophic niche segregation among mesopelagic species was pronounced and non‐overlapping groups could be distinguished because of the different vertical distribution and migratory behaviour. The study highlights the important role of the benthic boundary layer in sustaining benthopelagic communities in the deep Mediterranean Sea and the need to study the biology of a species throughout its whole depth range and not just at exploited depths ( i.e . fishing grounds).

Direct ageing of Thunnus thynnus from the eastern Atlantic Ocean and western Mediterranean Sea using dorsal fin spines - P. L. Luque; E. Rodriguez‐Marin; J. Landa; M. Ruiz; P. Quelle; D. Macias; J. M. Ortiz De Urbina (Journal of Fish Biology, 2014)
This study deals with important methodology issues that affect age estimates of eastern Atlantic bluefin tuna Thunnus thynnus using dorsal fin spines. Nearly 3800 spine sections were used from fish caught in the north‐east Atlantic Ocean and western Mediterranean Sea over a 21 year period. Edge type and marginal increment analyses indicated a yearly periodicity of annulus formation with the translucent bands (50% of occurrence) appearing from October to May. Nucleus vascularization seriously affected specimens older than 6 years, with the disappearance of 40–50% of the presumed annuli by that age. An alternate sectioning location was a clear improvement and this finding is an important contribution to the methodology of using this structure for ageing the full‐length range of eastern T. thynnus . Finally, there were no significant differences between the coefficients of von Bertalanffy growth model estimated from mean length at age data ( L ∞ = 327·4; k = 0·097; t 0 = −0·838) and those estimated from the growth curves accepted for the eastern and western T. thynnus management units.

Rainfall and temperatures changes have confounding impacts on P hytophthora cinnamomi occurrence risk in the southwestern USA under climate change scenarios - Sally E. Thompson; Simon Levin; Ignacio Rodriguez‐Iturbe (Global Change Biology, 2014)
Global change will simultaneously impact many aspects of climate, with the potential to exacerbate the risks posed by plant pathogens to agriculture and the natural environment; yet, most studies that explore climate impacts on plant pathogen ranges consider individual climatic factors separately. In this study, we adopt a stochastic modeling approach to address multiple pathways by which climate can constrain the range of the generalist plant pathogen P hytophthora cinnamomi (Pc): through changing winter soil temperatures affecting pathogen survival; spring soil temperatures and thus pathogen metabolic rates; and changing spring soil moisture conditions and thus pathogen growth rates through host root systems. We apply this model to the southwestern USA for contemporary and plausible future climate scenarios and evaluate the changes in the potential range of Pc. The results indicate that the plausible range of this pathogen in the southwestern USA extends over approximately 200 000 km 2 under contemporary conditions. While warming temperatures as projected by the IPCC A2 and B1 emissions scenarios greatly expand the range over which the pathogen can survive winter, projected reductions in spring rainfall reduce its feasible habitat, leading to spatially complex patterns of changing risk. The study demonstrates that temperature and rainfall changes associated with possible climate futures in the southwestern USA have confounding impacts on the range of Pc, suggesting that projections of future pathogen dynamics and ranges should account for multiple pathways of climate–pathogen interaction.

Comparative study of fuzzy evidential reasoning and fuzzy rule-based approaches: an illustration for water quality assessment in distribution networks - E. Aghaarabi; F. Aminravan; R. Sadiq; M. Hoorfar; M. J. Rodriguez; H. Najjaran (Stochastic Environmental Research and Risk Assessment, 2014)

Ruminal epithelium transcriptome dynamics in response to plane of nutrition and age in young Holstein calves - Aisha Naeem; James K. Drackley; Jennifer Stamey Lanier; Robin E. Everts; Sandra L. Rodriguez-Zas; Juan J. Loor (Functional & Integrative Genomics, 2014)

High-quality conforming hexahedral meshes of patient-specific abdominal aortic aneurysms including their intraluminal thrombi - J. Tarjuelo-Gutierrez; B. Rodriguez-Vila; D. M. Pierce; T. E. Fastl; P. Verbrugghe; I. Fourneau; G. Maleux; P. Herijgers; G. A. Holzapfel; E. J. Gomez (Medical & Biological Engineering & Computing, 2014)

Brassica Plant Responses to Mild Herbivore Stress Elicited by Two Specialist Insects from Different Feeding Guilds - P. Sotelo; E. Pérez; A. Najar-Rodriguez; A. Walter; S. Dorn (Journal of Chemical Ecology, 2014)

Genetic variation within a dominant shrub structures green and brown community assemblages - Gregory M. Crutsinger; Mariano A. Rodriguez-Cabal; Adam B. Roddy; Kabir G. Peay; Justin L. Bastow; Allison G. Kidder; Todd E. Dawson; Paul V. A. Fine; Jennifer A. Rudgers (Ecology, 2014)
Two rising challenges in ecology are understanding the linkages between above‐ and belowground components of terrestrial ecosystems and connecting genes to their ecological consequences. Here, we blend these emerging perspectives using a long‐term common‐garden experiment in a coastal dune ecosystem, whose dominant shrub species, Baccharis pilularis , exists as erect or prostrate architectural morphotypes. We explored variation in green (foliage‐based) and brown (detritus‐based) community assemblages, local ecosystem processes, and understory microclimate between the two morphs. Prostrate morphs supported more individuals, species, and different compositions of foliage arthropods, litter microarthropods, and soil bacteria than erect morphs. The magnitude of community compositional differences was maintained from crown to litter to soil. Despite showing strikingly similar responses, green and brown assemblages were associated with different underlying mechanisms. Differences in estimated shrub biomass best explained variation in the green assemblage, while understory abiotic conditions accounted for variation in the brown assemblage. Prostrate morphs produced more biomass and litter, which corresponded with their strong lateral growth in a windy environment. Compared to erect morphs, the denser canopy and thicker litter layer of prostrate morphs helped create more humid understory conditions. As a result, decomposition rates were higher under prostrate shrubs, despite prostrate litter being of poorer quality. Together, our results support the hypothesis that intraspecific genetic variation in primary producers is a key mediator of above‐ and belowground linkages, and that integrating the two perspectives can lead to new insights into how terrestrial communities are linked with ecosystem pools and processes.

A regulated deficit irrigation strategy for hedgerow olive orchards with high plant density - José E. Fernández; Alfonso Perez-Martin; José M. Torres-Ruiz; María V. Cuevas; Celia M. Rodriguez-Dominguez; Sheren Elsayed-Farag; Ana Morales-Sillero; José M. García; Virginia Hernandez-Santana; Antonio Diaz-Espejo (Plant and Soil, 2013)

Optimization of a Trap for Tuta absoluta Meyrick (Lepidoptera: Gelechiidae) and Trials to Determine the Effectiveness of Mass Trapping - E Lobos; M Occhionero; D Werenitzky; J Fernandez; L M Gonzalez; C Rodriguez; C Calvo; G Lopez; A C Oehlschlager (Neotropical Entomology, 2013)

Experiments using new initial soil moisture conditions and soil map in the Eta model over La Plata Basin - Moira E. Doyle; Javier Tomasella; Daniel A. Rodriguez; Sin Chan Chou (Meteorology and Atmospheric Physics, 2013)

The importance of progressive senescence in the biomass dynamics of giant kelp ( Macrocystis pyrifera ) - Gabriel E. Rodriguez; Andrew Rassweiler; Daniel C. Reed; Sally J. Holbrook (Ecology, 2013)
Temporal variation in primary producer biomass has profound effects on the structure and function of the surrounding ecological community. The giant kelp ( Macrocystis pyrifera ) exhibits strong intra‐annual variation in biomass density, which is better explained by the demographic rates of fronds than by those of whole plants. To better understand the processes controlling the dynamics of giant kelp fronds we collected monthly time‐series data of frond initiation and survival. These data were used to determine how frond loss and frond initiation rates were predicted by factors thought to affect the growth and survival of Macrocystis , including external environmental factors (i.e., wave height, day length, temperature, nutrient concentration, and neighborhood density) and intrinsic biological characteristics (i.e., frond age, plant size, and nutritional status). Our results revealed that frond dynamics were better explained by intrinsic biological processes rather than external environmental factors. A metric of frond age structure that incorporated progressive senescence was the best predictor of frond loss rate, accounting for 58% of the explained variation in frond loss. A similar analysis revealed that frond age structure was also the single best predictor of frond initiation rate, accounting for 46% of the explained variation. To further examine the importance of senescence in biomass dynamics, we used frond age‐dependent mortality and frond initiation rates to predict biomass in subsequent months and found that the model explained 73% of the observed variation in biomass at our sites. Vegetation dynamics of many species including giant kelp are often considered largely in the context of external controls on resource availability and physical disturbance. Our results indicate that investigations of the processes controlling vegetation dynamics may benefit greatly from the inclusion of intrinsic biological factors such as age‐dependent mortality and growth, which can outweigh the effects of external forcing in accounting for fluctuations in vegetation biomass.

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

Assessing water stress in a hedgerow olive orchard from sap flow and trunk diameter measurements - M. V. Cuevas; M. J. Martín-Palomo; A. Diaz-Espejo; J. M. Torres-Ruiz; C. M. Rodriguez-Dominguez; A. Perez-Martin; R. Pino-Mejías; J. E. Fernández (Irrigation Science, 2013)

Relationship between hydraulic conductance and citrus dwarfing by the Flying Dragon rootstock (Poncirus trifoliata L. Raft var. monstruosa) - B. Martínez-Alcántara; J. Rodriguez-Gamir; M. R. Martínez-Cuenca; D. J. Iglesias; E. Primo-Millo; M. A. Forner-Giner (Trees, 2013)

Investigations into the differential reactivity of endogenous and exogenous mercury species in coastal sediments - S. Bouchet; P. Rodriguez-Gonzalez; R. Bridou; M. Monperrus; E. Tessier; P. Anschutz; R. Guyoneaud; D. Amouroux (Environmental Science and Pollution Research, 2013)

Arbuscular mycorrhizal fungal community differs between a coexisting native shrub and introduced annual grass - Ryan R. Busby; Mary E. Stromberger; Giselle Rodriguez; Dick L. Gebhart; Mark W. Paschke (Mycorrhiza, 2013)

Cr(VI) Adsorption and Desorption on Soils and Biosorbents - M. T. Fernández-Pazos; B. Garrido-Rodriguez; J. C. Nóvoa-Muñoz; M. Arias-Estévez; M. J. Fernández-Sanjurjo; A. Núñez-Delgado; E. Álvarez (Water, Air, & Soil Pollution, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Kinetics of biodegradation of diesel fuel by enriched microbial consortia from polluted soils - E. Moliterni; R. G. Jiménez-Tusset; M. Villar Rayo; L. Rodriguez; F. J. Fernández; J. Villaseñor (International Journal of Environmental Science and Technology, 2012)

Zygomycosis Caused by Rhizopus microsporus and Rhizopus oryzae in Madhya Pradesh (M.P.) Central India: A Report of Two Cases - Shesh R. Nawange; S. M. Singh; J. Naidu; S. Jain; T. Nagpal; D. S. Behrani; E. Mellado; J. L. Rodriguez Tudela (Mycopathologia, 2012)

BK virus infection in human immunodeficiency virus-infected patients - J. Ledesma; P. Muñoz; D. Garcia de Viedma; I. Cabrero; B. Loeches; P. Montilla; P. Gijon; B. Rodriguez-Sanchez; E. Bouza (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Feasibility of Different Bioremediation Strategies for Treatment of Clayey and Silty Soils Recently Polluted with Diesel Hydrocarbons - E. Moliterni; L. Rodriguez; F. J. Fernández; J. Villaseñor (Water, Air, & Soil Pollution, 2012)

Doubled haploids in tropical maize: II. Quantitative genetic parameters for testcross performance - Vanessa Prigge; Raman Babu; Biswanath Das; M. Hernández Rodriguez; Gary N. Atlin; Albrecht E. Melchinger (Euphytica, 2012)

Modified Natural Clinoptilolite Detoxifies Small Mammal’s Organism Loaded with Lead II: Genetic, Cell, and Physiological Effects - Margarita Topashka-Ancheva; Michaela Beltcheva; Roumiana Metcheva; J. Antonio Heredia Rojas; Abraham O. Rodriguez-De la Fuente; Tsvetelina Gerasimova; Laura E. Rodríguez-Flores; Svetla E. Teodorova (Biological Trace Element Research, 2012)

Molecular characterization of Staphylococcus aureus from outpatients in the Caribbean reveals the presence of pandemic clones - A.-C. Uhlemann; C. Dumortier; C. Hafer; B. S. Taylor; J. Sánchez E.; C. Rodriguez-Taveras; P. Leon; R. Rojas; C. Olive; F. D. Lowy (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Concentration dependence of NaCl ion distributions around DPPC lipid bilayers - Jorge R. Rodriguez; Angel E. García (Interdisciplinary Sciences: Computational Life Sciences, 2011)

CIGB-300, a synthetic peptide-based drug that targets the CK2 phosphoaceptor domain. Translational and clinical research - Silvio E. Perea; Idania Baladron; Yanelda Garcia; Yasser Perera; Adlin Lopez; Jorge L. Soriano; Noyde Batista; Aley Palau; Ignacio Hernández; Hernán Farina; Idrian Garcia; Lidia Gonzalez; et al. (Molecular and Cellular Biochemistry, 2011)

Characterization of root-nodulating bacteria associated to Prosopis farcta growing in the arid regions of Tunisia - A. Fterich; M. Mahdhi; M. A. Caviedes; E. Pajuelo; R. Rivas; I. D. Rodriguez-Llorente; M. Mars (Archives of Microbiology, 2011)

Microbial diversity associated with four functional groups of benthic reef algae and the reef‐building coral Montastraea annularis - Katie L. Barott; Beltran Rodriguez‐Brito; Jan Janouškovec; Kristen L. Marhaver; Jennifer E. Smith; Patrick Keeling; Forest L. Rohwer (Environmental Microbiology, 2011)
Summary The coral reef benthos is primarily colonized by corals and algae, which are often in direct competition with one another for space. Numerous studies have shown that coral‐associated Bacteria are different from the surrounding seawater and are at least partially species specific (i.e. the same bacterial species on the same coral species). Here we extend these microbial studies to four of the major ecological functional groups of algae found on coral reefs: upright and encrusting calcifying algae, fleshy algae, and turf algae, and compare the results to the communities found on the reef‐building coral Montastraea annularis . It was found using 16S rDNA tag pyrosequencing that the different algal genera harbour characteristic bacterial communities, and these communities were generally more diverse than those found on corals. While the majority of coral‐associated Bacteria were related to known heterotrophs, primarily consuming carbon‐rich coral mucus, algal‐associated communities harboured a high percentage of autotrophs. The majority of algal‐associated autotrophic Bacteria were Cyanobacteria and may be important for nitrogen cycling on the algae. There was also a rich diversity of photosynthetic eukaryotes associated with the algae, including protists, diatoms, and other groups of microalgae. Together, these observations support the hypothesis that coral reefs are a vast landscape of distinctive microbial communities and extend the holobiont concept to benthic algae.

Effect of human-mediated migration and hybridization on the recovery of the American crocodile in Florida (USA) - David Rodriguez; Michael R. J. Forstner; Paul E. Moler; Joseph A. Wasilewski; Michael S. Cherkiss; Llewellyn D. Densmore III (Conservation Genetics, 2011)

Healthy eating index and ovarian cancer risk - Urmila Chandran; Elisa V. Bandera; Melony G. Williams-King; Lisa E. Paddock; Lorna Rodriguez-Rodriguez; Shou-En Lu; Shameka Faulkner; Katherine Pulick; Sara H. Olson (Cancer Causes & Control, 2011)

Transferase activity function and system development process are critical in cattle embryo development - Heather A. Adams; Bruce R. Southey; Robin E. Everts; Sadie L. Marjani; Cindy X. Tian; Harris A. Lewin; Sandra L. Rodriguez-Zas (Functional & Integrative Genomics, 2011)

Predisposition of cows to mastitis in non-infected mammary glands: effects of dietary-induced negative energy balance during mid-lactation on immune-related genes - Kasey M. Moyes; James K. Drackley; Dawn E. Morin; Sandra L. Rodriguez-Zas; Robin E. Everts; Harris A. Lewin; Juan J. Loor (Functional & Integrative Genomics, 2011)

Effect of the Antimicrobial Peptide Tritrpticin on the In Vitro Viability and Growth of Trichomonas vaginalis - Veronica V. Infante; Alma D. Miranda-Olvera; Luis M. De Leon-Rodriguez; Fernando Anaya-Velazquez; Mayra C. Rodriguez; Eva E. Avila (Current Microbiology, 2011)

A novel amino acid substitution in the para-sodium channel gene in Rhipicephalus microplus (Acari: Ixodidae) associated with knockdown resistance - Marcelino Aguirre; Adriana E. Flores; Genoveva Álvarez; Alberto Molina; Iram Rodriguez; Gustavo Ponce (Experimental and Applied Acarology, 2010)

Presence of Symbiodinium spp. in macroalgal microhabitats from the southern Great Barrier Reef - D. E. Venera-Ponton; G. Diaz-Pulido; M. Rodriguez-Lanetty; O. Hoegh-Guldberg (Coral Reefs, 2010)

Bond-based linear indices of the non-stochastic and stochastic edge-adjacency matrix. 1. Theory and modeling of ChemPhys properties of organic molecules - Yovani Marrero-Ponce; Eugenio R. Martínez-Albelo; Gerardo M. Casañola-Martín; Juan A. Castillo-Garit; Yunaimy Echevería-Díaz; Vicente Romero Zaldivar; Jan Tygat; José E. Rodriguez Borges; Ramón García-Domenech; Francisco Torrens; Facundo Pérez-Giménez (Molecular Diversity, 2010)

Cost-efficient management of coastal aquifers via recharge with treated wastewater and desalination of brackish groundwater: application to the Akrotiri basin and aquifer, Cyprus - A. D. Koussis; E. Georgopoulou; A. Kotronarou; K. Mazi; P. Restrepo; G. Destouni; C. Prieto; J. J. Rodriguez; J. Rodriguez-Mirasol; T. Cordero; C. Ioannou; A. Georgiou; et al. (Hydrological Sciences Journal, 2010)

Cost-efficient management of coastal aquifers via recharge with treated wastewater and desalination of brackish groundwater: general framework - A. D. Koussis; E. Georgopoulou; A. Kotronarou; D. P. Lalas; P. Restrepo; G. Destouni; C. Prieto; J. J. Rodriguez; J. Rodriguez-Mirasol; T. Cordero; A. Gomez-Gotor (Hydrological Sciences Journal, 2010)

The possible origin of Zostera noltii in the Canary Islands and guidelines for restoration - O. E. Diekmann; L. Gouveia; J. A. Perez; C. Gil-Rodriguez; E. A. Serrão (Marine Biology, 2010)

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

Mismatch repair protein expression and colorectal cancer in Hispanics from Puerto Rico - Wilfredo E. De Jesus-Monge; Carmen Gonzalez-Keelan; Ronghua Zhao; Stanley R. Hamilton; Miguel Rodriguez-Bigas; Marcia Cruz-Correa (Familial Cancer, 2010)

Season and size effects: changes in the quality of gilthead sea bream (Sparus aurata L.) - R. RODRIGUEZ; E. FOUNTOULAKI; K. GRIGORAKIS; M. ALEXIS; R. FLOS (Mediterranean Marine Science, 2010)
The aim of this study was to investigate the potential effects of the harvesting season and fish size on the final quality of cage farmed gilthead sea bream (Sparus aurata). Morphometric analysis, fat stores estimation, fillet composition analysis, fillet fatty acids profile determination and sensory analysis were carried out on a commercially-sized cage farmed gilthead sea bream (Sparus aurata L.) population in April, June, July and November. Both season and size had a significant effect in morphometric characteristics. The most pronounced size effect was the change of fish shape, becoming rounder with fish growth, the increase of filleting yield and condition index. An increase of both peritoneal and perivisceral fat was observed in summer months. In general size had little effect on muscle composition. A significant size effect was observed in the fillet lipid content, which increased with it. Fillet lipid content was unexpected lower in the warm period (June-July). This can be possibly attributed to feeding restrictions that may have occurred, due to anoxic incidents related to high temperatures.Slight seasonal differentiations occurred in the muscle fatty acids. No significant differences were found in the organoleptic characteristics of the two size groups compared.

Ploidy levels of Dioscorea alata L. germplasm determined by flow cytometry - J. Obidiegwu; E. Rodriguez; E. Ene-Obong; J. Loureiro; C. Muoneke; C. Santos; M. Kolesnikova-Allen; R. Asiedu (Genetic Resources and Crop Evolution, 2010)

Seed treatments enhance photosynthesis in maize seedlings by reducing infection with Fusarium spp. and consequent disease development in maize - C. Rodriguez-Brljevich; C. Kanobe; J. F. Shanahan; A. E. Robertson (European Journal of Plant Pathology, 2010)

Ploidy level studies on the Dioscorea cayenensis/Dioscorea rotundata complex core set - J. Obidiegwu; J. Loureiro; E. Ene-Obong; E. Rodriguez; M. Kolesnikova-Allen; C. Santos; C. Muoneke; R. Asiedu (Euphytica, 2009)

Family history of various cancers and pancreatic cancer mortality in a large cohort - Eric J. Jacobs; Carmen Rodriguez; Christina C. Newton; Elizabeth B. Bain; Alpa V. Patel; Heather Spencer Feigelson; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2009)

Enhancement of the antioxidants ergothioneine and selenium in Pleurotus eryngii var. eryngii basidiomata through cultural practices - Alma E. Rodriguez Estrada; Hyun-Ju Lee; Robert B. Beelman; Maria del Mar Jimenez-Gasco; Daniel J. Royse (World Journal of Microbiology and Biotechnology, 2009)

A Genomewide Assessment of Inbreeding Depression: Gene Number, Function, and Mode of Action - JULIEN F. AYROLES; KIMBERLY A. HUGHES; KEVIN C. ROWE; MELISSA M. REEDY; SANDRA L. RODRIGUEZ‐ZAS; JENNY M. DRNEVICH; CARLA E. CÁCERES; KEN N. PAIGE (Conservation Biology, 2009)
Although the genetic basis of inbreeding depression is still being debated, most fitness effects are thought to be the result of increased homozygosity for recessive or partially recessive deleterious alleles rather than the loss of overdominant genes. It is unknown how many loci are associated with inbreeding depression, the genes or gene pathways involved, or their mode of action. To uncover genes associated with variation in fitness following inbreeding, we generated a set of inbred lines of Drosophila melanogaster for which only the third chromosome varied among lines and measured male competitive reproductive success among these lines to estimate inbreeding depression. Male competitive reproductive success for different lines validated our prediction that equally inbred lines show variation in inbreeding depression. To begin to assess the molecular basis of inbreeding depression for male competitive reproductive success, we detected variation in whole‐genome gene expression across these inbred lines with commercially available high‐density oligonucleotide microarrays. A total of 567 genes were differentially expressed among these inbred lines, indicating that inbreeding directly or indirectly affects a large number of genes: genes that are disproportionately involved in metabolism, stress and defense responses. Subsequently, we generated a set of outbred lines by crossing the highest inbreeding depression lines to each other and contrasted gene expression between parental inbred lines and F 1 hybrids with transcript abundance as a quantitative phenotype to determine the mode of action of the genes associated with inbreeding depression. Although our results indicated that approximately 75% of all genes involved in inbreeding depression were additive, partially additive, or dominant, about 25% of all genes expressed patterns of overdominance. These results should be viewed with caution given that they may be confounded by issues of statistical inference or associative overdominance.

Use of blood-pressure-lowering medication and risk of prostate cancer in the Cancer Prevention Study II Nutrition Cohort - Carmen Rodriguez; Eric J. Jacobs; Anusila Deka; Alpa V. Patel; Elizabeth B. Bain; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2009)

Melatonin concentrations during larval and postlarval development of gilthead sea bream Sparus auratus : more than a time‐keeping molecule? - H. Kalamarz; M. Nietrzeba; J. Fuentes; G. Martinez‐Rodriguez; J.M. Mancera; E. Kulczykowska (Journal of Fish Biology, 2009)
In this study, melatonin (MEL) and thyroxine (T 4 ) concentrations were measured during larval and postlarval development of gilthead sea bream Sparus auratus Hormones were measured in whole bodies of larvae or the head and trunk of postlarvae after 67 days of exposure to constant light, 24L:0D, constant darkness, 0L:24D or 12L:12D and in the plasma of 6 month juveniles kept under the 12L:12D, 0L:24D and 24L:0D regimes. High MEL concentrations in larvae suggested a distinct role of MEL in early organogenesis and development of S. auratus . In larvae, the gastro‐intestinal tract seemed to be an important extrapineal and extraretinal source of MEL. No endogenous rhythm of MEL synthesis was demonstrated in 67 day larvae; however, in 6 month juveniles, it was evident. At early ontogenesis of S. auratus , the role of MEL is probably related mostly to the control of development and protection against free radicals, whereas its action as a time‐keeping molecule develops later. The increase in T 4 concentration during the S. auratus larva–juvenile transition, i.e . between 50 and 70 days post‐hatch, which was observed concurrently with the decrease of MEL concentration, may suggest an inverse relationship between T 4 and MEL.

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Molecular characterization of a foot-and-mouth disease virus containing a 57-nucleotide insertion in the 3′untranslated region - M. E. Piccone; S. Pauszek; J. Pacheco; E. Rieder; E. Kramer; L. L. Rodriguez (Archives of Virology, 2009)

Overexpression of WUSCHEL in C. chinense causes ectopic morphogenesis - L. Y. Solís-Ramos; T. González-Estrada; S. Nahuath-Dzib; L. C. Zapata-Rodriguez; E. Castaño (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Inhaled aminoglycosides in cancer patients with ventilator-associated Gram-negative bacterial pneumonia: safety and feasibility in the era of escalating drug resistance - D. E. Ghannam; G. H. Rodriguez; I. I. Raad; A. Safdar (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Scintillometer Intercomparison Study—Continued - J. Kleissl; C. J. Watts; J. C. Rodriguez; S. Naif; E. R. Vivoni (Boundary-Layer Meteorology, 2009)

Herbivore-Induced Volatiles in the Perennial Shrub, Vaccinium corymbosum, and Their Role in Inter-branch Signaling - Cesar R. Rodriguez-Saona; Luis E. Rodriguez-Saona; Christopher J. Frost (Journal of Chemical Ecology, 2009)

Carbon metabolism in leaves of micropropagated sugarcane during acclimatization phase - Romelio Rodriguez; Carlos E. Aragon; Maritza Escalona; Justo L. Gonzalez-Olmedo; Yves Desjardins (In Vitro Cellular & Developmental Biology - Plant, 2008)

Transcriptional activity and distribution of splicing machinery elements during Hyacinthus orientalis pollen tube growth - K. Zienkiewicz; A. Zienkiewicz; M. I. Rodriguez-Garcia; D. J. Smoliński; M. Świdziński; E. Bednarska (Protoplasma, 2008)

CIGB-300, a novel proapoptotic peptide that impairs the CK2 phosphorylation and exhibits anticancer properties both in vitro and in vivo - Silvio E. Perea; Osvaldo Reyes; Idania Baladron; Yasser Perera; Hernán Farina; Jeovanis Gil; Arielis Rodriguez; Dania Bacardi; Jose L. Marcelo; Karelia Cosme; Marisol Cruz; Carmen Valenzuela; et al. (Molecular and Cellular Biochemistry, 2008)

Role of Copper and Homocysteine in Pressure Overload Heart Failure - William M. Hughes; Walter E. Rodriguez; Dorothea Rosenberger; Jing Chen; Utpal Sen; Neetu Tyagi; Karni S. Moshal; Thomas Vacek; Y. James Kang; Suresh C. Tyagi (Cardiovascular Toxicology, 2008)

Expression of WUSCHEL in Coffea canephora causes ectopic morphogenesis and increases somatic embryogenesis - A. Arroyo-Herrera; A. Ku Gonzalez; R. Canche Moo; F. R. Quiroz-Figueroa; V. M. Loyola-Vargas; L. C. Rodriguez-Zapata; C. Burgeff D′Hondt; V. M. Suárez-Solís; E. Castaño (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

A potential function of endocannabinoids in the selection of a navigation strategy by rats - Pavel E. Rueda-Orozco; Edgar Soria-Gomez; Corinne J. Montes-Rodriguez; Marina Martínez-Vargas; Oscar Galicia; Luz Navarro; Oscar Prospero-García (Psychopharmacology, 2008)

The intake responses of three species of leaf-nosed Neotropical bats - Jorge Ayala-Berdon; Jorge E. Schondube; Kathryn E. Stoner; Nelly Rodriguez-Peña; Carlos Martínez Del Río (Journal of Comparative Physiology B, 2008)

Characteristics of Streptococcus bovis endocarditis and its differences with Streptococcus viridans endocarditis - J. Corredoira; M. P. Alonso; A. Coira; E. Casariego; C. Arias; D. Alonso; J. Pita; A. Rodriguez; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Characterization of typo-, regio-, and stereo-selectivities of babaco latex lipase in aqueous and organic media - E. Cambon; J. A. Rodriguez; M. Pina; V. Arondel; F. Carriere; F. Turon; J. Ruales; P. Villeneuve (Biotechnology Letters, 2008)

Simultaneous use of the X‐ and Y‐chromosome genes SMCX , SMCY , and DBY for sex determination in the Florida manatee ( Trichechus manatus latirostris ) - Michael D. Tringali; Michelle C. Davis; Marta A. Rodriguez‐lopez; Ellen E. Bolen; Jamie G. Sullivan; Elsa M. Haubold (Marine Mammal Science, 2008)

Competing demands for irrigation water: golf and agriculture in Spain - J. A. Rodriguez Diaz; J. W. Knox; E. K. Weatherhead (Irrigation and Drainage, 2007)
In many countries where water resources are under stress, there is a perception that irrigating golf courses causes significant additional abstraction, and that this has major impacts on the environment and other abstractors, including irrigated agriculture. This paper provides a quantitative assessment of water use within the golf sector in Spain, and compares it with irrigated agriculture. It is based on literature review, a national survey of golf course irrigation practices, and a correlation of reported irrigation consumption against agroclimate. Using a geographical information system (GIS), the water consumption for all golf courses in Spain was modelled and mapped, and the total water consumption estimated. The results show that the volume of water used for golf irrigation is extremely small compared to agricultural irrigation. Furthermore, a significant portion comes from wastewater reuse (41%) and desalination (7%), rather than direct abstraction, which competes with agriculture. However, it is concentrated in particular tourist areas and could cause local problems. The average economic productivity of the water used for golf, estimated at around 9 € m −3 in direct benefits (course fees) and 28 € m −3 if including the benefits to the tourist industry, is very much higher than for even high‐value agricultural crops. These results suggest that irrigating golf courses for tourism purposes is an economically rational water use in Spain, even though the transfer of resources from agriculture is controversial. Copyright © 2007 John Wiley & Sons, Ltd.

A marker-assisted backcross approach for developing submergence-tolerant rice cultivars - C. N. Neeraja; R. Maghirang-Rodriguez; A. Pamplona; S. Heuer; B. C. Y. Collard; E. M. Septiningsih; G. Vergara; D. Sanchez; K. Xu; A. M. Ismail; D. J. Mackill (Theoretical and Applied Genetics, 2007)

Aquifer Vulnerability Zoning, an Indicator of Atmospheric Pollutants Input? Vanadium in the Salamanca Aquifer, Mexico - J. A. Mejia; R. Rodriguez; A. Armienta; E. Mata; A. Fiorucci (Water, Air, & Soil Pollution, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Lack of evidence for effect modification by estrogen of association between body mass index and colorectal cancer risk among postmenopausal women - Yiting Wang; Eric J. Jacobs; Lauren R. Teras; Alexandre L. Pavluck; Carmen Rodriguez; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2007)

Owl monkey MHC-DRB exon 2 reveals high similarity with several HLA-DRB lineages - Carlos F. Suárez; Manuel E. Patarroyo; Esperanza Trujillo; Mónica Estupiñán; Juan E. Baquero; Carlos Parra; Raúl Rodriguez (Immunogenetics, 2006)

Nuclear DNA content of Vitis vinifera cultivars and ploidy level analyses of somatic embryo-derived plants obtained from anther culture - F. Leal; J. Loureiro; E. Rodriguez; M. S. Pais; C. Santos; O. Pinto-Carnide (Plant Cell Reports, 2006)

A Polymerase Chain Reaction Screening Method for Rapid Detection of Microsatellites in Bacterial Artificial Chromosomes - M. F. Rodriguez; S. A. Gahr; C. E. Rexroad; Y. Palti (Marine Biotechnology, 2006)

Owl monkey MHC-DRB exon 2 reveals high similarity with several HLA-DRB lineages - Carlos F. Suárez; Manuel E. Patarroyo; Esperanza Trujillo; Mónica Estupiñán; Juan E. Baquero; Carlos Parra; Raúl Rodriguez (Immunogenetics, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

Propensity for paternal inheritance of de novo mutations in Alexander disease - Rong Li; Anne B. Johnson; Gajja S. Salomons; Marjo S. van der Knaap; Diana Rodriguez; Odile Boespflug-Tanguy; J. Rafael Gorospe; James E. Goldman; Albee Messing; Michael Brenner (Human Genetics, 2006)

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

Genome-wide SNP discovery and linkage analysis in barley based on genes responsive to abiotic stress - Nils Rostoks; Sharon Mudie; Linda Cardle; Joanne Russell; Luke Ramsay; Allan Booth; Jan T. Svensson; Steve I. Wanamaker; Harkamal Walia; Edmundo M. Rodriguez; Peter E. Hedley; Hui Liu; et al. (Molecular Genetics and Genomics, 2005)

Parity, Other Reproductive Factors, and Risk of Pancreatic Cancer Mortality in a Large Cohort of U.S. Women (United States) - Lauren R. Teras; Alpa V. Patel; Carmen Rodriguez; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2005)

Melatonin increases the survival time of animals with untreated mammary tumours: Neuroendocrine stabilization - M. C. Saez; C. Barriga; J. J. Garcia; A. B. Rodriguez; J. Masot; E. Duran; E. Ortega (Molecular and Cellular Biochemistry, 2005)

Behavioral alterations in lewis rats following two-day continuous 3-nitropropionic acid administration - J. D. Newcomb; W. D. Brown; A. I. Rodriguez; S. Garbuzova-Davis; S. Saporta; P. R. Sanberg; A. E. Willing (Neurotoxicity Research, 2005)

Use of multivitamins and prostate cancer mortality in a large cohort of US men - Victoria L. Stevens; Marjorie L. McCullough; W. Ryan. Diver; Carmen Rodriguez; Eric J. Jacobs; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2005)

Photosynthesis and carbon metabolism in plantain (Musa AAB) plantlets growing in temporary immersion bioreactors and during ex vitro acclimatization - Carlos E. Aragón; Maritza Escalona; Iris Capote; Danilo Pina; Inaudis Cejas; Roberto Rodriguez; Maria Jesus Cañal; Jorge Sandoval; Sophe Roels; Pierre Debergh; Justo Gonzalez-Olmedo (In Vitro Cellular & Developmental Biology - Plant, 2005)

Clinical characteristics and significance of Streptococcus salivarius bacteremia and Streptococcus bovis bacteremia: a prospective 16-year study - J. C. Corredoira; M. P. Alonso; J. F. García; E. Casariego; A. Coira; A. Rodriguez; J. Pita; C. Louzao; B. Pombo; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Dengue virus type 2 in Cuba, 1997: conservation of E gene sequence in isolates obtained at different times during the epidemic - R. Rodriguez-Roche; M. Alvarez; T. Gritsun; D. Rosario; S. Halstead; G. Kouri; E. A. Gould; M. G. Guzman (Archives of Virology, 2005)

Secondary metabolites from endophytic fungi isolated from the Chilean gymnosperm Prumnopitys andina (Lleuque) - G. Schmeda-Hirschmann; E. Hormazabal; L. Astudillo; J. Rodriguez; C. Theoduloz (World Journal of Microbiology and Biotechnology, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Environmental Education as a Component of Multidisciplinary Conservation Programs: Lessons from Conservation Initiatives for Critically Endangered Fruit Bats in the Western Indian Ocean - W. J. TREWHELLA; K. M. RODRIGUEZ‐CLARK; N. CORP; A. ENTWISTLE; S. R. T. GARRETT; E. GRANEK; K. L. LENGEL; M. J. RABOUDE; P. F. REASON; B. J. SEWALL (Conservation Biology, 2005)
Pteropus livingstonii , P. voeltzkowi , and P. rodricensis are three critically endangered fruit bats from western Indian Ocean islands for which multidisciplinary conservation programs have been established that include environmental education programs (EEPs). We describe these EEPs in terms of the strategies used to achieve them and evaluate the educational and conservation outcomes and impacts of the programs. Educational outputs (including posters, stickers, videos, lesson plans, and workshops), primarily linking human needs to the ecosystem services provided by bats, were delivered to schools and community groups, and local environmental educators were trained to further develop the EEPs. Outcomes included increased local awareness about the bats and their conservation, training of environmental educators, inclusion of bat conservation and environmental issues in the school curricula, and establishment of community‐based environmental nongovernmental organizations (NGOs). Extensive prior planning, presentations in local languages, distribution of outputs through existing networks of educators, training of local educators, establishment of local environmental NGOs, and local capacity‐building were all associated with these EEPs achieving their goals in the under‐resourced island locations where these bats are found. The EEPs were also important in the development of other components of their respective conservation programs, such as population monitoring programs. Although long‐term conservation impacts, particularly tackling habitat loss, are slow to materialize and social and economic issues need to be addressed, these EEPs have already had important outcomes and have established the foundation for future conservation actions.

Reevaluation of the earthquakes of 10 March and 19 May 1951 in southern Spain - A. Udías; D. Muñoz; E. Buforn; C. Sanz de Galdeano; C. del Fresno; I. Rodriguez (Journal of Seismology, 2005)

Prostate cancer incidence and survival in relation to education (United States) - Kyle Steenland; Carmen Rodriguez; Alison Mondul; Eugenia E. Calle (Cancer Causes & Control, 2004)

Decline in Assayable Progesterone in Bovine Serum under Different Storage Conditions - T. de Castro; L. Valdez; M. Rodriguez; N. Benquet; E. Rubianes (Tropical Animal Health and Production, 2004)

FEEDING ECOLOGY OF THE MARINE OTTER ( LUTRA FELINA ) IN A ROCKY SEASHORE OF THE SOUTH OF CHILE - Gonzalo Medina‐Vogel; Claudio Delgado Rodriguez; P. Ricardo E. Alvarez; V. Jose Luis Bartheld (Marine Mammal Science, 2004)
A bstract The marine otter ( Lutra felina ) lives exclusively along exposed rocky shorelines on the South American Pacific coast from Peru (6°S), to Cape Horn, Chile (56°S), and Isla de los Estados, Argentina. L. felina diet and its relationship to prey availability and energy content was assessed by spraint and prey remains analysis, direct observation, and the use of crab pots and fish traps, at four sites on the Valdivian coast in the south of Chile, between June 1999 and June 2000. Based on spraints analysis, the diet was composed of 25 species; 52% (13/25) of the species identified were crustaceans, 40% (10/25) were fish, and 8% (2/25) were mollusks. Crustaceans were found in 78% of 475 spraints, 100% of 929 prey remains, and 90.8% of prey determined by direct observation, fish in 20% of spraints and 9.0% of prey determined by direct observation, and mollusks in 2% of spraints and 0.2% of prey determined by direct observation. Observed seasonal variation in prey availability was reflected in the otter diet. Fourteen prey species were trapped; 43% (6/14) were crustaceans and 57% (8/14) fish, crustaceans were 93% of 566 trapped individuals, fish 7%. L. felina showed opportunistic feeding behavior, selecting prey seasonally according to their availability rather than to their energy input.

A comparative study of the expression of monoamine oxidase-A and -B mRNA and protein in non-CNS human tissues - S. D. Sivasubramaniam; C. C. Finch; M. J. Rodriguez; N. Mahy; E. E. Billett (Cell and Tissue Research, 2003)

Integration of soil solarization with chemical, biological and cultural control for the management of soilborne diseases of vegetables - C. Stevens; V. A. Khan; R. Rodriguez-Kabana; L. D. Ploper; P. A. Backman; D. J. Collins; J. E. Brown; M. A. Wilson; E. C. K. Igwegbe (Plant and Soil, 2003)

Calcium, vitamin D, dairy products, and risk of colorectal cancer in the Cancer Prevention Study II Nutrition Cohort (United States) - Marjorie L. McCullough; Andrea S. Robertson; Carmen Rodriguez; Eric J. Jacobs; Ann Chao; Carolyn Jonas; Eugenia E. Calle; Walter C. Willett; Michael J. Thun (Cancer Causes & Control, 2003)

An Evolutionary Approach to Understanding the Biology of Invasions: Local Adaptation and General‐Purpose Genotypes in the Weed Verbascum thapsus - Ingrid M. Parker; Joseph Rodriguez; Michael E. Loik (Conservation Biology, 2003)
The role of evolution in the invasion of non‐native species has important implications for conservation, weed science, risk assessment, and policy. In this paper we first discuss why an evolutionary perspective can be helpful and outline a range of potentially useful approaches from population biology and ecological genetics. As a case study, we then ask how adaptation and genetic structure may promote or constrain the expansion of an invasive weed, Verbascum thapsus , into high elevations in the Sierra Nevada of California. We used growth‐chamber and common‐garden experiments to assay a range of morphological and physiological traits that could influence plant fitness at high elevation. There was a significant relationship between elevation and leaf size and reflectance above 800 m, although we found no relationship between elevation and most other traits ( growth rate in warm or cool temperatures, freezing tolerance when grown in warm or cool temperatures, leaf number, rosette morphology, plant height ). We did see marked genetic differentiation among populations, possibly reflecting founder effects and a history of genetic drift. When we partitioned the phenotypic variance, there was almost no variation among maternal families within populations, limiting the potential for selection to act. The majority of the variance for all traits was among individuals within families, suggesting that environmental conditions strongly influenced the phenotype. Overall, the increasing success of V. thapsus at high elevations appears to conform more to Baker's concept of a general‐purpose genotype than to invasion by rapid adaptation.

Effects of Sertoli cell transplants in a 3-nitropropionic acid model of early Huntington's disease: a preliminary study - Alba I. Rodriguez; Alison E. Willing; Samuel Saporta; Don F. Cameron; Paul R. Sanberg (Neurotoxicity Research, 2003)

Ultrastructure of the host-pathogen interface in daylily leaves infected by the rust fungus Puccinia hemerocallidis - C. W. Mims; C. Rodriguez-Lother; E. A. Richardson (Protoplasma, 2002)

Body mass index, height, and postmenopausal breast cancer mortality in a prospective cohort of US women - Jennifer M. Petrelli; Eugenia E. Calle; Carmen Rodriguez; Michael J. Thun (Cancer Causes & Control, 2002)

Jewish ethnicity and prostate cancer mortality in two large US cohorts - Carmen Rodriguez; Eric J. Jacobs; Alpa V. Patel; Eugenia E. Calle; Heather Spencer Feigelson; Dorna Fakhrabadi-Shokoohi; Michael J. Thun (Cancer Causes & Control, 2002)

Multivitamin use and colon cancer mortality in the Cancer Prevention Study II cohort (United States) - Eric J. Jacobs; Cari J. Connell; Alpa V. Patel; Ann Chao; Carmen Rodriguez; Jennifer Seymour; Marjorie L. McCullough; Eugenia E. Calle; Michael J. Thun (Cancer Causes & Control, 2001)

Identification of genomic regions that affect grain-mould incidence and other traits of agronomic importance in sorghum - R. R. Klein; R. Rodriguez-Herrera; J. A. Schlueter; P. E. Klein; Z. H. Yu; W. L. Rooney (Theoretical and Applied Genetics, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Tubal sterilization and risk of breast cancer mortality in US women - Eugenia E. Calle; Carmen Rodriguez; Kimberly A. Walker; Phyllis A. Wingo; Jennifer M. Petrelli; Michael J. Thun (Cancer Causes & Control, 2001)

A novel approach for the definition of the inorganic medium components for micropropagation of yellow passionfruit (Passiflora edulis sims. F. Flavicarpa Deg.) - A. C. B. de A. Monteiro; E. N. Higashi; A. N. Gonçalves; A. P. M. Rodriguez (In Vitro Cellular & Developmental Biology - Plant, 2000)

Ecotoxicological Assessment of Two Pulp Mill Effluent, Biobio River Basin, Chile - H. Gaete; A. Larrain; E. Bay-Schmith; J. Baeza; J. Rodriguez (Bulletin of Environmental Contamination and Toxicology, 2000)

Ecotoxicological Assessment of Two Pulp Mill Effluent, Biobio River Basin, Chile - H. Gaete; A. Larrain; E. Bay-Schmith; J. Baeza; J. Rodriguez (Bulletin of Environmental Contamination and Toxicology, 2000)

Linkage mapping and QTL analysis in coconut (Cocos nucifera L.) - A. Herrán; L. Estioko; D. Becker; M. J. B. Rodriguez; W. Rohde; E. Ritter (Theoretical and Applied Genetics, 2000)

Transformation of floral organs with GFP in Medicago truncatula - K. Kamaté; I. D. Rodriguez-Llorente; M. Scholte; P. Durand; P. Ratet; E. Kondorosi; A. Kondorosi; T. H. Trinh (Plant Cell Reports, 2000)

El Niño influence on streamflow forecasting - J. Kelman; A. de M. Vieira; J. E. Rodriguez-Amaya (Stochastic Environmental Research and Risk Assessment, 2000)

Behavior of Brick Samples in Aggressive Environments - G. Cultrone; M. J. De la Torre; E. M. Sebastian; O. Cazalla; C. Rodriguez-Navarro (Water, Air, & Soil Pollution, 2000)

Immunoglobulin kappa light-chain V , J , and C gene sequences of the owl monkey Aotus nancymaae - O. L. Diaz; C. A. Daubenberger; R. Rodriguez; M. Naegeli; A. Moreno; M. E. Patarroyo; G. Pluschke (Immunogenetics, 2000)

Synthesis and characterization of Sodium cis-dichlorochenodeoxycholylglycinato(O,N) platinum(II) – Cytostatic activity - Julio J. Criado; M.C. Garcia-Moreno; Rocio R. Macias; Jose J.G. Marin; Manuel Medarde; E. Rodriguez-Fernandez (BioMetals, 1999)

Nitrogen and Sulfur Deposition and Forest Nutrient Status in the Valley of Mexico - M. E. Fenn; L. I. de Bauer; A. Quevedo-Nolasco; C. Rodriguez-Frausto (Water, Air, & Soil Pollution, 1999)

Structure and function of the stalk, a putative regulatory element of the yeast ribosome. Role of stalk protein phosphorylation - M. A. Rodriguez-Gabriel; G. Bou; E. Briones; R. Zambrano; M. Remacha; J. P. G. Ballesta (Folia Microbiologica, 1999)

Relative and combined effects of ethanol and protein deficiency on strontium and barium bone content and fecal and urinary excretion - E. Gonzalez-Reimers; F. Rodriguez-Moreno; A. Martinez-Riera; A. Mas-Pascual; E. Delgado-Ureta; L. Galindo-Martin; M. Arnay-de La Rosa; F. Santolaria-Fernandez (Biological Trace Element Research, 1999)

Monthly mean pressure reconstructions for Europe for the 1780–1995 period - P.D. Jones; T.D. Davies; D.H. Lister; V. Slonosky; T. Jónsson; L. Bärring; P. Jönsson; P. Maheras; F. Kolyva‐Machera; M. Barriendos; J. Martin‐Vide; R. Rodriguez; et al. (International Journal of Climatology, 1999)

Infertility and risk of fatal ovarian cancer in a prospective cohort of US women - Carmen Rodriguez; Lilith M. Tatham; Eugenia E. Calle; Michael J. Thun; Eric J. Jacobs; Clark W. Heath (Cancer Causes & Control, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Diabetes mellitus and pancreaticcancer mortality in a prospectivecohort of United States adults - Eugenia E. Calle; Terrell K. Murphy; Carmen Rodriguez; Michael J. Thun; Clark W. Heath (Cancer Causes & Control, 1998)

The corticostriatal system mediates the "paradoxical" contraversive rotation but not the striatal hyperexpression of Fos induced by amphetamine early after 6-hydroxydopamine lesion of the nigrostriatal pathway - E. Lopez-Martin; G. Rozas; J. Rodriguez; M. J. Guerra; J. L. Labandeira-Garcia (Experimental Brain Research, 1998)

Isolation by distance in Germany - I. Barrai; C. Scapoli; M. Beretta; C. Nesti; E. Mamolini; A. Rodriguez-Larralde (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Differential effects of ventilatory stimulation by sex hormones and almitrine on hypoxic erythrocytosis - R. Favier; H. Spielvogel; E. Caceres; A. Rodriguez; B. Sempore; J. Pequignot; J. M. Pequignot (Pflügers Archiv - European Journal of Physiology, 1997)

Influence of potato composition on chip color quality - Luis E. Rodriguez-Saona; Ronald E. Wrolstad (American Journal of Potato Research, 1997)

Influence of gender and endogenous sex steroids on catecholaminergic structures involved in physiological adaptation to hypoxia - J. M. Pequignot; H. Spielvogel; E. Caceres; A. Rodriguez; B. Semporé; J. Pequignot; R. Favier (Pflügers Archiv - European Journal of Physiology, 1997)

Inhibition of Various Cholinesterases with the Enantiomers of Malaoxon - O. P. Rodriguez; G. W. Muth; C. E. Berkman; K. Kim; C. M. Thompson (Bulletin of Environmental Contamination and Toxicology, 1997)

Oral immunization of rabbits with VP60 particles confers protection against rabbit hemorrhagic disease - J. Plana-Duran; M. Bastons; M. J. Rodriguez; I. Climent; E. Cortés; C. Vela; I. Casal (Archives of Virology, 1996)

Human acetylator genotype: Relationship to colorectal cancer incidence and arylamine N-acetyltransferase expression in colon cytosol - Jose W. Rodriguez; Ward G. Kirlin; Ronald J. Ferguson; Mark A. Doll; Kevin Gray; Timothy D. Rustan; Mark E. Lee; Katherine Kemp; Paul Urso; David W. Hein (Archives of Toxicology, 1993)

Genetic analysis of nonhistone chromosomal protein inheritance in recombinant inbred mouse strains using two-dimensional electrophoresis - Louis S. Ramagli; James E. Womack; Lewis V. Rodriguez (Biochemical Genetics, 1990)

Beta interferon production in primed and unprimed cells infected with human cytomegalovirus - J. E. Rodriguez; T. R. Loepfe; N. S. Swack (Archives of Virology, 1987)

Human cytomegalovirus persists in cells treated with interferon - J. E. Rodriguez; T. R. Loepfe; M. F. Stinski (Archives of Virology, 1983)

Imide derivatives of 3-nitro-1.8-naphthalic acid: Their inhibitory activity against DNA viruses - A. Garca Gancedo; C. Gil-Fernndez; P. Vilas; S. Perez; E. Paez; F. Rodriguez; M. F. Braa; C. M. Roldn (Archives of Virology, 1982)

Clinical, virological, and pathological features of herpesvirus SA8 infection in conventional and gnotobiotic infant baboons(Papio cynocephalus) - J. W. Eichberg; B. McCullough; S. S. Kalter; D. E. Thor; A. R. Rodriguez (Archives of Virology, 1976)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)